QSRR-Based RP-HPLC Method Development for Antiviral Drug Analysis: Machine Learning, Design of Experiments, and Sustainable Analytical Strategies—A Review - Pawan Kumar Goswami; Sonakshi Antal; Arvind Kumar Patel (Journal of Pharmaceutical Innovation, 2027)

Challenges and Opportunities with CRISPR-Based Genome Editing in Legume Crops - Pawan Kumar; Himanshu Yadav; Badal Mahakalkar; Rushil Mandlik; Sanskriti Vats; Vandana Thakral; Virender Kumar; Saurabh Kumar Nishad; Satish Nichal; Rupesh Deshmukh; Tilak Raj Sharma; Humira Sonah (Functional & Integrative Genomics, 2026)

Breaking the permeability-selectivity-fouling trade-off: Electroconductive PES-LIG-GO composite membrane with integrated passive and active biofouling control - Kritika Jashrapuria; Utkarsh Misra; Pawan Kumar; Swatantra P. Singh (Chemical Engineering Journal, 2026)

Analyzing integrated knowledge, attitudes and practices for the adoption of blast-resistant wheat varieties in Bangladesh: A structural equation modeling approach - Nasima Akter; Hasneen Jahan; Md Abdullah Al Noman; Md Monirul Islam; M. Wakilur Rahman; Sadika Haque; Pawan Kumar Singh; Muhammad Rezaul Kabir; Nanda Dulal Kundu (Crop Protection, 2026)

Effect of air and N2 dilution on combustion stability and emission in a swirl stabilized premixed combustor operating on H2 and mixtures of H2 and CH4 - Pawan Kumar Ojha; Dan Michaels; Alexander Lazebnikov; Boris Chudnovsky (Fuel, 2026)

Greenhouse gas emissions: trends, impacts, and global mitigation approaches - Sushmita; Amandeep Kaur; Amanpreet Kaur; Pawan Kumar (Arabian Journal of Geosciences, 2026)

Organoids in polycystic ovary syndrome: Emerging platforms and future directions - Ishanka Singh; Anuja Pant; Pawan Kumar Maurya (Reproductive Biology, 2026)

Cosmic ray intensity variations and geomagnetic activity during 1996–2025 - Pawan Kumar; Sham Singh (Advances in Space Research, 2026)

Impact of seedling stage waterlogging stress on yield traits of sesame and selection of superior genotypes using multivariate analysis - Pawan Kumar Prajapati; Vijay Sharma; Mukul Kumar; Kamaluddin; Chandra Mohan Singh; Shalesh Kumar Singh; Arun Kumar; Vishal Chugh; Vaishali Gangwar; Priya Sharma; Harsh Jainth; Mohd Irshad Ali; et al. (Plant Physiology Reports, 2026)

Chromatography-free GREEN quantification of first-line anti-TB drugs using FTIR–PLS - Saurabh B. Pawar; Pavan kumar Sathala; Jayesh; Laltanpuii Chenkual; Arindam Senapati; Pawan Kumar Porwal (Sustainable Chemistry and Pharmacy, 2026)

Tuneable silver ion mobility in silver-laser-induced graphene composites for safer water disinfection: Role of co-ions and electrical potential - Nandini Dixit; Pawan Kumar; Swatantra P. Singh (Process Safety and Environmental Protection, 2026)

Dating feldspar micro-inclusions within quartz emphasizing on the dose rate: An alternate way to date Himalayan Quaternary deposits - Priyanka Singh; Madhav K. Murari; Sheikh N. Ali; S.K. Pandey; Pawan Govil; Sarajit Sensarma; Kamlesh Kumar; Siddharth Prizomwala; Anupam Sharma; Ipsita Roy; R. Jayangondaperumal; Parminder Ranhotra; et al. (Quaternary Geochronology, 2026)

Rediscovering nutritional wealth of ancient Indian dwarf wheat (Triticum sphaerococcum Percival) against modern bread wheat for starch components, glycemic index and micronutrient content - K. Prathibha; Amit Kumar Mazumder; C.K. Mohammed Salman; Rakesh Kumar; Gauri Andhale; Chinmay Behera; Deepanyeta Goswami; Sanjay Kumar Singh; Manjeet Kumar; Prashanth Babu; Shiv Kumar Singh; Kunal Kumar; et al. (Journal of Cereal Science, 2026)

Current Paradigms in Understanding Neuron Fluctuations, Factors, Regulation, Pathophysiology of Epilepsy: Advancements in Diagnosis, Treatment and Management—An Update - Pooja Sharma; Payal Gupta; Anita Rani Gill; Sunil Kumar; Pawan Kumar; Paavan Singhal; Mahiti Gupta; Raj Singh; Varruchi Sharma; Sharun Khan; Kuldeep Dhama; Ajay Sharma; et al. (Indian Journal of Clinical Biochemistry, 2026)

Bridging tradition and modernity: socio-climatic determinants and farmers’ perceptions of agroforestry adoption in the hilly regions of Himachal Pradesh - Pawan Kumar; Yash Pal; Amar Latta (Agroforestry Systems, 2026)

Integrated Transcriptomic and Small RNA Profiling Reveals Regulatory Networks Associated With Seed Protein Accumulation in Chickpea (Cicer arietinum L.) - Gopal Kalwan; Deshika Kohli; Yashwant Kumar Yadava; Sheel Yadav; Suruchi Khanna; Ila Joshi; MS Nimmy; S. V. Amitha Mithra; Biswajit Mondal; Shailesh Tripathi; Satvir Kaur Grewal; Kishor Gaikwad; et al. (Journal of Plant Growth Regulation, 2026)

Acacia nilotica Linn. bark extract as wood bio-preservative: GC-MS analysis and bioactive assessment - Pawan Kumar Poonia; Mamta Khaiper; Reena Chouhan; Sushil Kumari; Manjeet Singh; Urmila; Mohammed Nasir; Himshikha Gusain (Next Research, 2026)

Resistance-guided isolation and identification of antibiotic-resistant bacteria from bull semen: exploring alternatives to antibiotics in semen extenders - Dileep Kumar Yadav; H. M. Rashmi; Manisha Sethi; Ramasamy Arunkumar; Pawan Singh; Nishant Kumar (Tropical Animal Health and Production, 2026)

In silico and in vitro insights into stigmasterol targeting Keap1/Nrf2, Bcl-2/Bax and IKKβ/IκBα protein–protein interactions in Arsenic-induced toxicity - Manoj Soni; Vivek Kumar; Yangala Sudheer Babu; Pawan Kumar; Mulaka Maruthi; Pooja Yadav; Ajit Kumar; Vijay Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Revisiting endometriosis management: Polyphenols as alternative therapeutic candidates - Anuja Pant; Kareena Moar; Reetu Hooda; Pawan Kumar Maurya (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Engineering optimism: affective dynamics and field emergence in the UK’s driverless vehicle transition - Pawan Kumar Srikanth (Environmental Innovation and Societal Transitions, 2026)

Genetic association of C677T in MTHFR and T3801C in CYP1A1 with the risk of breast cancer in the North Indian population: a case–control study - Ishan Behlam; Amrit Sudershan; Shikha Bharti; Adesh K. Saini; Sunita Manhas; Surbhi Pathania; Mohd Younis; Rachna Sabharwal; Pawan Kumar; Parvinder Kumar (The Nucleus, 2026)

Probiotics: A Promising Microbial Functional Food with Diverse Health Benefits - Harshita Srivastav; Aman Kumar; Pawan Kumar Bhargawa; Neha Vishnoi; Rajesh Kumar (Probiotics and Antimicrobial Proteins, 2026)

Benthic meiofaunal community structure from a recently discovered hydrothermal field on a seamount, Andaman Sea, Indian Ocean - Gourav Kumar Mishra; Sabyasachi Sautya; Sriram Gullapalli; Pawan Dewangan; Umesh Pradhan; Gunjan Sarkar; Sanofar Khokar; Amita Choudhury (Marine Biology, 2026)

Impact of Excessive Moisture on Amoxycillin Content in Amoxycillin and Potassium Clavulanate Dry Oral Suspensions Marketed in High-Humidity Regions of India: A Pharmacopoeial Study - Pawan Kumar; Pawan Kumar Saini; Saurabh Sahoo; Rajeev Singh Raghuvanshi; Gaurav Pratap Singh Jadaun (Journal of Pharmaceutical Innovation, 2026)

Evolutionary Study of Transposable Elements: Structural Characterization and Phylogenomic Profiling in Plant Genomes - Pawan Kumar Jayaswal; Nagendra Kumar Singh (Journal of Molecular Evolution, 2026)

Fungal cellulases: a comprehensive review on production, innovations, and applications - Mahima; Varsha Rani; Kunwar Vishal; Pawan Kumar Doharey; Aiman Tanveer; Pramod K. Yadav; Dinesh Yadav (Archives of Microbiology, 2026)

Artificial Intelligence, Machine Learning, and Multi-omics: The Future of Cancer and Precision Oncology - Kareena Moar; Anuja Pant; Pawan Kumar Maurya (Indian Journal of Clinical Biochemistry, 2026)

Hydrogeochemical characterization, spatial distribution, and suitability of groundwater for drinking and irrigation in the Aravalli Range, Haryana, India - Manoj Kumar; Anoop Yadav; Manjeet Bansal; Vinod Kumar Garg; Pawan Kumar Rose; Ram Pravesh Kumar; Bhupendra P. Singh (Environmental Sustainability, 2026)

Residual Content Impacts Critical Quality Attributes and Performance of Risperidone Microspheres - Saurabh Bhorkade; Bo Wan; Pawan Kumar Pandey; Sia Dhruva; Diane Burgess (Pharmaceutical Research, 2026)

Silicon and nano‑silicon mediated sustainable management of invasive fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae): A comprehensive review - Yakshith D.S.; Gouranga Saw; Mallikarjuna Jeer; Sridhar Jandrajupalli; Pankaj Sharma; Pawan Kumar Agrawal; Pramod Kumar Rai (Pesticide Biochemistry and Physiology, 2026)

Comprehensive lipidomics reveal Rotenone exposure induces redox-driven lipid droplet accumulation, systemic lipidome perturbation and differential metabolic prioritization linked to Parkinson’s disease - Ashutosh K. Tiwari; Priya Rathor; Rajendra Patel; Pawan Kumar Jha; Nick Birse; Ratnasekhar CH (NeuroToxicology, 2026)

Advanced flexible composite films of Ti₃C₂Tₓ MXene-CCTO-PVDF for high-performance TENG-based self-powered sensor applications - Amar Dev; Amod Kumar; Tupan Das; Pawan Kumar; S.K. Pradhan; P. Kour; Manoranjan Kar (Chemical Engineering Journal, 2026)

Seasonal variations in leaf essential oil of Eucalyptus tereticornis clones: Yield, composition analysis and antioxidant potential - Mamta Khaiper; Pawan Kumar Poonia; Sunil Kumar Dhanda; Preety Verma; Anjali Tiwari; Vikas Kumar (Biomass and Bioenergy, 2026)

Smart farming approaches in medicinal plant cultivation: a review of techniques, benefits, and sustainability - Sanjeev Khan; Nutan Pathania; Pawan Kumar; Rahul Kumar; Jitender Kumar; Nitesh Kumar; Arti Sharma (Planta, 2026)

Incorporation of network pharmacology, molecular docking, survival, density functional theory, and experimental studies to explore the potential key targets of formononetin by TERT-mediated anti-cancer effects in MCF-7 breast cancer - Rohit Singh Negi; Amit Kumar Singh; Adarsh Kumar Pathak; Rakesh Kumar Gupta; Nitish Kumar; Jyotirmayee Behera; Manjeet Kumar Sah Gond; Anand Kumar Singh; Pawan Kumar Dubey; Sunil Kumar Mishra (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Assessing Landscape Dynamics and Variations in Land Surface Temperature in the Parbati Watershed of the Himalayas - Pawan Kumar Thakur; Raj Kumar Verma; Praveen Kumar Thakur; Suraj Kumar Mallick; Biswajeet Pradhan; Ranjeet Kumar (International Journal of Environmental Research, 2026)
Land-Use/Land-Cover (LULC) plays a crucial role in environmental management, yet its dynamic changes, especially in mountainous regions, remain inadequately studied. Sustainable land management requires comprehensive policies integrating environmental sustainability, climate resilience, and socioeconomic factors. However, the lack of Strategic Environmental Assessment (SEA) often leads to fragmented policies. This study examines LULC changes and their impact on Land Surface Temperature (LST) in the Parbati Watershed (PW), Northwestern Himalayas, focusing on human-induced vegetation changes and policy effectiveness. LULC changes from 2001 to 2021 were analyzed using Landsat satellite imagery and spectral indices such as Normalized Difference Vegetation Index (NDVI) and LST. LULC maps were generated using Support Vector Machine (SVM) classification algorithm to ensure high accuracy and robustness. LST was extracted from Landsat Thematic Mapper (TM), Enhanced Thematic Mapper Plus (ETM+), and Operational Land Imager (OLI) data using the split-window algorithm (SW), which accounts for surface emissivity and reduces atmospheric interference. Linear regression models assessed the relationship between LST and NDVI in relation to LULC classes. Results indicate a decline in glaciers/snow (⁓-6.37%), Himalayan moist temperate forests (HMTF), (⁓-0.21%), Himalayan dry temperate forests (HDTF), (⁓-0.07%), vegetation/grass/grazing areas (⁓-0.86%), and water bodies (⁓-0.18%). Conversely, built-up/settlements areas, agricultural/plantations land, barren/sandy lands and rocky/open/debris land increased by ⁓0.15%, ⁓0.28%, ⁓0.24% and ⁓6.47%, respectively. Strong correlations were observed between LST and NDVI in built-up/settlement class (R²=0.63) and barren/sandy areas (R²=0.87) in 2021. Accurate retrieval of LST is essential for monitoring urban heat islands (UHI), deforestation, and agricultural expansion, particularly in the context of rapid climate change and intensified anthropogenic activities impacting various LULC classes. This study advances climate adaptation and sustainable land management by integrating LST analysis with landscape dynamics. The findings offer valuable insights for policymakers, supporting the development of effective climate resilience strategies and informed infrastructure planning. Graphical abstract

Macrophage-targeted Hyaluronic-acid Coated Liposomes Bearing Ursolic Acid for Visceral Leishmaniasis: In Vitro Characterisation and Pharmacokinetic Analysis - Spandana Gollapalli; Soyal Sayyed; Pawan Devangan; Dinesh Kumar Chandanpalli; Nandkumar Doijad; Rahul Kumar; Jitender Madan (Current Microbiology, 2026)

Serum Biochemical and Gene Expression Changes in the Spermatozoa of Buffalo Bulls Under Heat Stress - Rashi Vasisth; Karpenahalli Ranganatha Sriranga; Meenakshi Chitkara; Ankita Gurao; Lalit Pratap Singh; Mahesh Shivanand Dige; Monika Sodhi; Manishi Mukesh; Pradeep Kumar; Pawan Singh; Ranjit Singh Kataria (Biochemical Genetics, 2026)

Stimuli-Responsive Carbon Nanotubes for On-Demand Cancer Therapy: A Review - Mahendran Radha; Ragini Shubham Chaudhari; Mayuresh Kashinath Raut; Mallepally Mamatha; Disha Arora; Akhilesh Patel; Shamim Shamim; Pawan Kumar (AAPS PharmSciTech, 2026)

Microbial fuel cell powered Fenton degradation of ciprofloxacin from wastewater employing MIL-88B(Fe)-MOF-laser-induced graphene cathode - Azhan Ahmad; Pawan Kumar; Bhavana Kanwar; Swatantra P. Singh (Environmental Research, 2026)

Impact of Long-Term Fertilization Practices on Weed Flora Diversity in Typic Hapludalf Soils - Pawan Kumar; Sachin Kumar; Surinder Singh Rana; Raj Paul Sharma; Narender Kumar Sankhyan; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2026)

Impact of biomedicinal substrate supplementation on the cultivation of Schizophyllum commune Fries - Nitika Chauhan; Dharmesh Gupta; Debjeet Sharma; Pawan Kumar Sharma (Indian Phytopathology, 2026)

Identification of QTLs Responsible for Fodder Quality Traits in Fodder Maize (Zea mays L.) - Pawan Kumar Dash; Palaniyappan Subramani; Ganesan Kalipatty Nalliappan; Manivannan Narayana; Vellaikumar Sampathrajan; Senthil Natesan (Indian Journal of Genetics and Plant Breeding, 2026)

A benchmark UPLC-based method for concurrent analysis of seventeen Stevia rebaudiana metabolites (steviol, isosteviol, and fifteen steviol glycosides) in a single analytical run and its implementation in diverse products - Pawan Kumar; Anmol; Sahil Awasthi; Rajiv Kumar Tonk; Mohit Sharma; Upendra Sharma (Food Research International, 2026)

Assessing ecosystem health and governance challenges in Nagi and Nakti Ramsar sites: developing a framework for sustainable conservation - Suman Kumari; A. M. Sajina; R. K. Manna; B. K. Das; Pawan Kumar; Y. Ali (Wetlands Ecology and Management, 2026)

Constructed wetlands as sustainable solutions for textile effluent treatment: a review - Pawan Kumar Bhargawa; Shweta Tiwari; Saroj Kumar; Sampurna Nand; Rajesh Kumar (Physiology and Molecular Biology of Plants, 2026)

Temporal Modulation of Physiological and Biochemical Mechanisms Enhances Drought Tolerance Across Developmental Stages in Field Pea (Pisum sativum L.) - Amit Sharma; Ravika Sheoran; Rajesh Yadav; Pawan Kumar; Kavita Dhaka; Deepak Kaushik; Jyoti Duhan; Naresh (Journal of Plant Growth Regulation, 2026)

Poly(ε-Caprolactone) Microparticles of Andrographolide for Paracetamol-Induced Liver Iinjury: Box-Behnken Design Based Optimization, In Vitro and In Vivo Studies - Nitin Wadate; Pawan Devangan; Pankaj Kumar; Gopal Bajad; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

Indole-3-Acetic Acid Production and Molecular Insights into its Biosynthetic Pathway - Pradeep Kumar; Simran Rani; Priyanka Dahiya; Balwant Kaur; Pawan Kumar; Kiran Arora; Ajit Kumar; Amita Suneja Dang; Pooja Suneja (Indian Journal of Microbiology, 2026)

Evaluation of the heavy metal pollution in soil from Singrauli coal mine area, Madhya Pradesh, India - Vaishali Srivastava; Pawan Kumar Jha; Anil Kumar (Environmental Geochemistry and Health, 2026)

Magnesium oxide-functionalized biochar synthesis from municipal solid waste for Pb(II) removal in aqueous media and potential application in leachate remediation - Nkululeko Sabelo Dlamini; Pawan Kumar Jha; Pradeep Kumar Sharma (Environmental Science and Pollution Research, 2026)

Biomass-mediated nanomaterials for petroleum refinery waste remediation: a comprehensive review of mechanisms and applications - Shweta Tiwari; Pawan Kumar Bhargawa; Rajesh Kumar (Environmental Monitoring and Assessment, 2026)

Integrating CA–Markov–ANN for spatiotemporal prediction of land use dynamics in a fragile Himalayan watershed - Pawan Kumar Thakur; Praveen Kumar Thakur; Raj Kumar Verma; Biswajeet Pradhan (Remote Sensing Applications: Society and Environment, 2026)

Triumphing over hidden hunger: Redesigning rice (Oryza sativa L.) for enhanced nutraceutical grain composition utilizing multiplexed genome editing - Khaled Fathy; Jyotsna Bharti; Sonia Khan Sony; Mamta Nehra; Rashmi Kaul; Bhupendra Rawat; Sudhir K. Sopory; Pawan Kumar Agrawal; Arul Prakash; Tanushri Kaul (Journal of Plant Physiology, 2026)

Cs, Ba, Co, and Eu sorption on biotite - experiments at ambient temperature and modelling - Pawan Kumar; Stellan Holgersson; Christian Ekberg (Journal of Environmental Radioactivity, 2026)

Experimental and machine learning-based estimation of the thermal diffusivity of high-plastic soil - Pawan Kishor Sah; Divesh Ranjan Kumar; Shiv Shankar Kumar; Warit Wipulanusat (Geothermics, 2026)

A novel additive strategy using biomass derived biodiesel fueled with diphenylamine and ceria in diesel engine for emission mitigation and performance improvement - Vijay Kumar; Akhilesh Kumar Choudhary; Pawan Kumar Singotia (Biomass and Bioenergy, 2026)

Hydrological performance of ERA5 land in the data-scarce Himalayan region of the Langtang catchment - Ashish Devkota; Pawan Kumar Bhattarai; Vishnu Prasad Pandey; Subbarao Pichuka; Ananta Man Singh Pradhan; Susen Shrestha (Theoretical and Applied Climatology, 2026)

CFD-based optimization of a modified Savonius rotor with hybrid upstream deflector using Kriging surrogates and FA–GWO algorithm - Pulijala Pawan Kumar; Raj Kumar Singh (Ocean Engineering, 2025)

Co-infection with systemic candidiasis and diphtheritic aspergillosis in a Buffalo calf - Sumit S. Kamble; Veena R. Sutar; S. D. Vinay Kumar; Sonu S. Nair; V. Athira; J. Pranathi; Pawan Kumar; Prasad Thomas; Bablu Kumar; Premanshu Dandapat; Vidya Singh; Abhishek (Veterinary Research Communications, 2025)

Evaluation of stable reference genes for RT-qPCR analysis in Antheraea assamensis (Lepidoptera: Saturniidae) during pathogenic infections - Indumathi Kamatchi Balakrishnan; Himanshu Dubey; Pawan Shukla; Rajal Debnath; C. Vanitha; Gangavarapu Subrahmanyam; Manthira moorthy; Kallare P. Arunkumar; Vikram Kumar; Abhishek Singh; K. M. Ponnuvel (Molecular Biology Reports, 2025)

Elucidating the binding specificity of interactive compounds targeting ATP-binding cassette subfamily G member 2 (ABCG2) - Pawan Kumar; Indu Kumari; Rajendra Prasad; Shashikant Ray; Atanu Banerjee; Amresh Prakash (Molecular Diversity, 2025)

Insight into hydroponic nutrient solution mediated morpho-physiological, iridoid glycosides accumulation and gene expression modulations in Picrorhiza kurroa Royle ex Benth - Kanika; Ashrita; Shiv Shanker Pandey; Pawan Kumar; Dinesh Kumar; Ashish R. Warghat (Plant Biotechnology Reports, 2025)

Network pharmacology prediction of UA in targeting endometriosis progression to endometrial cancer - Jayhind Kumar Chauhan; Pradeep Kumar; Sangeeta Rai; Safiya Ayesha; Pawan K. Dubey; Anima Tripathi (In Silico Pharmacology, 2025)

Hydrochemistry and quality assessment of groundwater around Jawalamukhi Region, Himachal Pradesh, Northwest Himalaya, India - Richa Panjla; Ambrish Kumar Mahajan; Sanjay Pandey; Pawan Kumar (Environmental Science and Pollution Research, 2025)

Impact of satellite derived wind and LULC on coastal inundation: a sensitivity study for the east coast of India - Anup Kumar Mandal; Pawan Tiwari; Ambarukhana D. Rao; Rashmi Sharma; Prasad K. Bhaskaran (Natural Hazards, 2025)

Effect of different heat mitigation strategies on the thermography of lactating water buffaloes during summer seasons under tropical conditions - Manisha Choudhary; Lija Satheesan; Aarti Kamboj; Pritam Pal; Dheeraj Kumar; Pawan Singh; Ajay Kumar Dang (International Journal of Biometeorology, 2025)

Drainage basin analysis of Sunai River, Odisha, India: A remote sensing and GIS-based approach - Pawan Kumar Gautam; Dhirendra Kumar; Satyajit Sahu; Anoop Kumar Singh (Arabian Journal of Geosciences, 2025)

Longitudinal genomic and pedigree inbreeding metrics reveal inbreeding depression in milk quality traits of Sahiwal cattle maintained in organised herd - Jayesh Vyas; Ishmeet Kumar; Anil Chitra; Gargi Ramola; Sabyasachi Mukherjee; Indrajit Ganguly; Arun Kumar Mishra; Pawan Singh; Udita Chaudhary; Anupama Mukherjee (The Nucleus, 2025)

Estimation of actual evapotranspiration and stage-wise crop coefficients for transplanted rice using a modified non-weighing paddy lysimeter and their prediction on machine ensemble approach in the middle Indo-Gangetic plains of South Asia - Arti Kumari; Ashutosh Upadhyaya; Pawan Jeet; Rakesh Kumar; Kirti Saurabh; Ved Prakash; Anup Das; P. K. Sundaram; A. K. Singh; Akram Ahmed; Amit Kumar (Environment, Development and Sustainability, 2025)

Phospholipase C activator 3m3FBS reverses the synergistic toxicity of arsenic and cadmium - Manika Garg; Aiysha Siddiq Khan; Muskan Verma; Anupam Chawla; Pawan Yadav; Yogita Rawat; Asghar Ali; Somendu Kumar Roy; Mohan Kamthan (Journal of Trace Elements in Medicine and Biology, 2025)

PEGylation-based surface engineering of islets with microparticles co-delivery for enhanced engraftment in streptozocin-induced hyperglycemic murine model - Prakash Shrestha; Shiva Pathak; Dinesh Chaudhary; Shobha Regmi; Manju Shrestha; Pawan Kumar Raut; Ju-Yeon Kim; Gorka Orive; Ha Rin Kim; Na Kyeong Lee; Seho Kweon; Jooho Park; et al. (Chemical Engineering Journal, 2025)

Navigating Uncertainties in Quantifying Water Availability Amidst the Climate and Land Use Changes - Nirajan Devkota; Suraj Lamichhane; Pawan Kumar Bhattarai (Water Resources Management, 2025)

Spatial distribution and geochemical baseline concentration of potentially toxic elements from the north-western lesser himalayas, India - Subodh Verma; Sayam Konar; Arindam Das; Manmohan; Pawan Kumar; Kaleem Javed (Environmental Geochemistry and Health, 2025)

Lead and arsenic toxicity: emerging mechanisms, immunotoxic effects, and future research perspectives - Rahul Thakur; Sukhpal Singh; Aman Chauhan; Pawan Kumar; Reena V. Saini; Adesh K. Saini (BioMetals, 2025)

Ellagic Acid Displays a Protective Effect on Red Blood Cell Membrane During Aging in Humans - Deepika; Tikam Chand Dakal; Richa; Pawan Kumar Maurya (Indian Journal of Clinical Biochemistry, 2025)

Advanced OER catalysts: MnCo-LDH integrated with NiP2 and Ni5P4 metal phosphides for superior water splitting performance - Rahadian Zainul; Ali B.M. Ali; Tariq J. Al-Musawi; Anjan Kumar; Pawan Sharma; Shaxnoza Saydaxmetova; Reem Hamdan KHaddour; Abdulrahman A. Almehizia; Khursheed Muzammil (Applied Clay Science, 2025)

Diversity and abundance of rice hopper complex under natural farming in Himachal Pradesh, India - Aarushi Sharma; Pawan Kumar Sharma; Prem Chand Sharma; Ajay Sood; Arun Kumar (International Journal of Tropical Insect Science, 2025)

Network pharmacology and in silico analysis of Cucumis melo phytochemicals targeting ER stress in diabetic nephropathy - Mohammed Nazish Quasmi; Jiten Singh; Sanjay Yadav; Dinesh Kumar; Pawan Gupta; Ashok Jangra (In Silico Pharmacology, 2025)

Fenugreek seeds-generated exosome-like nanoparticles: An orally administrable green therapeutic approach for pain amelioration in primary dysmenorrhea-induced mice model - Amoolya Sree; Payel Chakraborty; Mythri Chandrasekaran; Dimple Sunilkumar Lalchandani; Kannan Shajkumar; Ankita Das; Afridi Shafik Chabru; Pawan Kumar Porwal; Sudhagar Selvaraju; Swapnil Jayant Dengale; Tamilvanan Shunmugaperumal (Next Research, 2025)

Dietary flavonoids in health and diseases: A concise review of their role in homeostasis and therapeutics - Aditi Mohan; Gurumurthy Dummi Mahadevan; Venkatesh Anand Iyer; Tapan Kumar Mukherjee; Vishal Haribhai Patel; Rajeev Kumar; Nahid Siddiqui; Manoranjan Nayak; Pawan Kumar Maurya; Prabhanshu Kumar (Food Chemistry, 2025)

Exploring the electronic modulation in controlling the activity and selectivity of Ni-Au-In based catalyst in atmospheric pressure CO2 hydrogenation - Jyotsna P. Bajpai; Sharad Gupta; Devender Goud; Diku Raj Deka; Anuradha V. Jagtap; Pawan Kumar; Momin Ahamed; Sebastian C. Peter; C.P. Vinod (Chemical Engineering Journal, 2025)

PiPho85, a cyclin-dependent kinase of Piriformospora indica rescue colonized maize plants grown under salt stress - Arun Kumar Kashyap; Paras Kumar; Aayushi Bajaj; Rupesh Aggarwal; Pawan Kumar Sharma; Pooja Panwar; Shubhankar Pandey; Vikas Yadav; Ralf Oelmuller; Meenakshi Dua; Atul Kumar Johri (World Journal of Microbiology and Biotechnology, 2025)

Plastic waste and residual waste management: a case study of the Pathum Thani dumpsite in Thailand - Pawan Kumar Srikanth; Suwanna Kitpati Boontanon; Chettiyappan Visvanathan (Waste Disposal & Sustainable Energy, 2025)

Stimuli-responsive Hydrogels for Targeted Antibiotic Delivery in Bone Tissue Engineering - Jayendra Kumar; Tolepbergenova M.; Abdugani Musayev; Aizhan Danyshbayeva; Lazzat Begimbekova; Hitesh Kumar; Terlikbayeva Gulnar; Pawan Kumar; Shamim Shamim (AAPS PharmSciTech, 2025)

Late Quaternary productivity and hydrographic variability in the upper water column of the Agulhas Return Current region as inferred from planktic foraminifera - Divya Verma; Pawan Govil; Shailesh Agrawal; P. Morthekai; Brijesh Kumar; Hidayatullah Khan (Quaternary International, 2025)

Seasonal variation in chemical composition and bioactivity of Eucalyptus tereticornis leaf essential oil - Mamta Khaiper; Pawan Kumar Poonia; Sunil Kumar Dhanda; Ravi Beniwal; Preety Verma; Mohammed Nasir (Biochemical Systematics and Ecology, 2025)

Heavy metal pollution assessment of groundwater and associated health risks around the coal mining area, Singrauli, Madhya Pradesh, India - Vaishali Srivastava; Pawan Kumar Jha; Anil Kumar (Environmental Monitoring and Assessment, 2025)

Biological and genomic characterization of a cypovirus isolated from golden muga silkworm, Antheraea assamensis Helfer (Lepidoptera: Saturniidae) - Iyyangar Deepika; Abhishek Singh; Indira Kumar; Gowtham K; Roja Gnanasekaran; Himanshu Dubey; Rajal Debnath; Pawan Shukla; Kangayam M. Ponnuvel; Vikram Kumar; K.P. Arunkumar; Hanamant Gadad; et al. (Journal of Invertebrate Pathology, 2025)

Effects of pH, ionic strength, and temperature on Cs, Ba, Co, and Eu sorption onto biotite: A combined experimental and modeling study - Pawan Kumar; Stellan Holgersson; Christian Ekberg (Journal of Contaminant Hydrology, 2025)

Trends and advances in liposome formulation technology with an emphasis on ensuring safety and quality in food and drug applications - Pawan Prabhakar; Soubhagya Tripathy; Deepak Kumar Verma; Smita Singh; Mamta Thakur; Amit Kumar Singh; Prem Prakash Srivastav; Mamoni Banerjee; Ami R. Patel; Mónica L. Chávez González; Gemilang Lara Utama; José Sandoval-Cortés; et al. (Food Bioscience, 2025)

Evaluation of mitochondrial copy number and gene expression changes in the spermatozoa of buffalo bulls under heat stress - Meenakshi Chitkara; Harsimran Kaur; Rashi Vasisth; Karpenahalli Ranganatha Sriranga; Ankita Gurao; Karan Mahar; Mahesh Shivanand Dige; R.A.K. Aggarwal; Manishi Mukesh; Pradeep Kumar; Pawan Singh; Ranjit Singh Kataria (Reproductive Biology, 2025)

Recent advancements in heterogeneous cathode catalysts for in-situ hydrogen peroxide synthesis in bio-electro-Fenton process and its application in wastewater treatment: A review - Azhan Ahmad; Pawan Kumar; Swatantra P. Singh (Journal of Environmental Chemical Engineering, 2025)

Exergy-energy, economic and environmental evaluation of a solid oxide fuel cell based trigeneration system using double effect vapor absorption refrigeration system - Yunis Khan; Pawan Kumar Singh; Aftab Anjum; K.K. Sivakumar; Shikha Gupta; Subhash Mishra (International Journal of Refrigeration, 2025)

QTL-Meta-analysis and Candidate Gene(s) for Anaerobic Germination Potential in Rice - Sanchika Snehi; Pawan Kumar Singh; R. Beena; Suneetha Kota; Satish Kumar Sanwal; K. T. Ravi Kiran; C. Anilkumar; Krishnendu Chattopadhyay; Nitish Ranjan Prakash; Rameswar Prasad Sah (Journal of Plant Growth Regulation, 2025)

Development of flow cytometry protocol and genome size estimation in heeng (Ferula assa-foetida L.) - Jyotsana Bishnoi; Amit Rana; Pawan Kumar; Ravi Kumar; Ashok Gehlot; Satbeer Singh; Ramesh Chauhan; Sanatsujat Singh; Ashok Kumar (Journal of Plant Biochemistry and Biotechnology, 2025)

Integrated Treatment of Textile Wastewater and Methyl Orange Azo Dye: Constructed Wetland-Based Remediation Enhanced by Bacterial Treatment - Pawan Kumar Bhargawa; Shweta Tiwari; Saroj Kumar; Rajesh Kumar (International Journal of Environmental Research, 2025)

Best linear unbiased prediction (BLUP)-based models aided in selection of high yielding charcoal rot and yellow mosaic resistant soybean genotypes - Pawan Kumar Amrate; Vennampally Nataraj; M. Shivakumar; M. K. Shrivastava; Laxman Singh Rajput; Salikram Mohare; Nisha Agrawal; Saloni Mandloi; Kumar Jai Anand; Milind B. Ratnaparkhe; K. Bhojaraja Naik; Sanjay Gupta; et al. (Genetic Resources and Crop Evolution, 2025)

Imidazopyridine Based Fluorescent Turn-Off Sensor for Selective Recognition of Fe3+ Ions and its Application in Test Strips - Akanksha Manhas; Sonakshi Sasan; Lalita Devi; Manu Sharma; Avtar Changotra; Pawan Kumar; Kamal K. Kapoor (Journal of Fluorescence, 2025)

A review of the genus Paranosia Lee 2014 (Hemiptera: Cicadidae) with the description of one new species from India - Babu Saddam; Jiali Wang; Pawan Kumar (International Journal of Tropical Insect Science, 2025)

Differential role of endogenous hormones and effect of exogenous hormonal-temperature treatments on seed dormancy and germination in Heeng (F. assa-foetida L.) and its wild relative F. jaeschkeana Vatke - Ravi Kumar; Amit Rana; Pawan Kumar; Shimran Yadav; Robin Joshi; Dinesh Kumar; Satbeer Singh; Ramesh Chauhan; Sanatsujat Singh; Ashok Kumar (South African Journal of Botany, 2025)

Development and performance analysis of structural lightweight aggregate self-compacting concrete: A sustainable solution - Pawan Kumar; Pasla Dinakar; T. Jothi Saravanan (Process Safety and Environmental Protection, 2025)

Evaluation of genotype × environment interactions for seed yield in field pea (Pisum sativum L.) genotypes using multivariate analysis model - Amit Sharma; Rajesh Yadav; Ravika Sheoran; Pawan Kumar; Deepak Kaushik; Kavita Dhaka; Nikhil Gangadharaiah; Arpit Sharma (Euphytica, 2025)

Geo-hydrological analysis and watershed delineation of the Sarayan River, Ganga Plain, India: integrating geospatial data for water resource management - Pawan Kumar Gautam; Narendra Kumar (Arabian Journal of Geosciences, 2025)

Environmental impacts of coal mining and mitigation measures: a review - Vaishali Srivastava; Pawan Kumar Jha (Environmental Monitoring and Assessment, 2025)

Disparate hypsometry and consequential recession pattern variations of the glaciers originating from a single source in the Himachal Himalaya, India - Sanjay Deswal; Satya Prakash; Elora Chakraborty; Milap Chand Sharma; Rakesh Saini; Parvendra Kumar; Padma Dalal; Pawan Kumar (Journal of Earth System Science, 2025)

Analysis of intense geomagnetic storm on 24 April 2023 with interplanetary parameters - Pawan Kumar; Mahender Pal; Sham Singh (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Chemometric quantification of trace element impurities within kaolin and talc white clay minerals in Kutch and Banas-Mahi basin, India - Prashant Shriram Wagh; Ravishankar Kumar; Sanjeev Bhasin; Pawan Pal (Arabian Journal of Geosciences, 2025)

Geochemistry and stable isotope (δ13C & δ18O) signatures of Calcrete in the Ganga Plains: Implications for paleoclimate and Paleovegetation patterns - Prasanna K; Sarkar Amrita; Amal M.S; Sharma Anupam; Rahi Ishwar Chandra; Kumar Kamlesh; Mathews Runcie Paul; Govil Pawan (Quaternary International, 2025)

Analysis 2023 Storms based on different time scales (Dst, Kp & Sym/H) - Pawan Kumar; Mahender Pal; A.P. Mishra; Sham Singh (Journal of Space Safety Engineering, 2025)

Climate change impacts on flood dynamics and seasonal flow variability in central Nepal: the Kaligandaki River Basin case - Koshish Raj Maharjan; Utsav Bhattarai; Pawan Kumar Bhattarai; Laxmi Prasad Devkota (Theoretical and Applied Climatology, 2025)

Gold Nanoparticles as a Tool to Detect Biomarkers in Osteoarthritis: New Insights - Atul Mourya; Shristi Arya; Ayush Singh; Gopal Bajad; Soham Loharkar; Shubhra; Pawan Devangan; Neelesh Kumar Mehra; Rahul Shukla; Ramesh Chandra; Jitender Madan (Indian Journal of Microbiology, 2025)

Western equatorial Indian Ocean surface hydrographic variations inferred from isotopic record of planktic foraminifera Globigerinoides ruber during last ~412,000 years - Brijesh Kumar; Pawan Govil; Shailesh Agrawal; Pankaj Kumar; Divya Verma; Hidayatullah Khan (Journal of Earth System Science, 2025)

Microplastics influencing aquatic environment and human health: A review of source, determination, distribution, removal, degradation, management strategy and future perspective - Pawan Kumar; Anil Kumar; Deepak Kumar; Kalp Bhusan Prajapati; Ambrish Kumar Mahajan; Deepak Pant; Anoop Yadav; Anand Giri; Satish Manda; Soniya Bhandari; Richa Panjla (Journal of Environmental Management, 2025)

Spectral light treatment and exogenous feeding of precursors enhanced the picrosides content in dedifferentiated cell culture of Picrorhiza kurroa - Mahinder Partap; Amit Kumar; Pawan Kumar; Dinesh Kumar; Ashish R. Warghat (Biocatalysis and Agricultural Biotechnology, 2025)

Deciphering the endomicrobiome of Podophyllum hexandrum to reveal the endophytic bacterial-association of in-planta podophyllotoxin biosynthesis - Manju Kumari; Anish Tamang; Mohit Swarnkar; Pawan Kumar; Dinesh Kumar; Ashish Rambau Warghat; Vipin Hallan; Shiv Shanker Pandey (World Journal of Microbiology and Biotechnology, 2025)

Scaffolds imparting anthelmintic activity: recent advancements and SAR studies - Pawan Kumar; Rohit Bhatia; Naresh Kumar Rangra (Molecular Diversity, 2025)

Phyto-Fingerprinting of Putranjiva roxburghii Wall. Leaf Extract and its In Vitro Anti-Inflammatory Activity - Jayhind Kumar Chauhan; Pradeep Kumar; Pawan K. Dubey; Anima Tripathi (Cell Biochemistry and Biophysics, 2025)

Silica Nanoparticles: A Promising Vehicle for Anti-Cancer Drugs Delivery - T. Naga Aparna; Rohit Kumar; Shah Raj Ali; Dhaval J. Patel; Kazi Julekha; Touseef Begum; Jyoti Bala; Pawan Kumar (AAPS PharmSciTech, 2025)

Minimizing the risk of ethylene glycol and diethylene glycol poisoning in medications: A regulatory and pharmacopoeial response - Pawan Kumar; Shruti Rastogi; Pawan Kumar Saini; Saurabh Sahoo; Rajeev Singh Raghuvanshi; Gaurav Pratap Singh Jadaun (Regulatory Toxicology and Pharmacology, 2025)

Elicitors Mediated Enhancement of Picrosides and Their Pathway Precursors in Dedifferentiated Cell Suspension Culture of Picrorhiza kurroa Royle ex Benth - Mahinder Partap; Amit Kumar; Pawan Kumar; Dinesh Kumar; Ashish R. Warghat (Journal of Plant Growth Regulation, 2025)

The genital morphology and major taxonomic characteristics of butterfly Genus Papilio (Lepidoptera: Papilionidae): insights from Northwestern Himalayas, India - Ritika Gangotia; Babu Saddam; Pawan Kumar (International Journal of Tropical Insect Science, 2024)

Phytophagous probiotic foods: Exploring the intersection of characteristics, quality implications, health benefits, and market dynamics - Alaa Kareem Niamah; Shayma Thyab Gddoa Al-Sahlany; Hussein Katai Abdul-Sada; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Smita Singh; Deepak Kumar Verma; Alok Kumar Gupta; Rakesh Mohan Shukla; Mamta Thakur; Ami R. Patel; et al. (Trends in Food Science & Technology, 2024)

Shatavarin-IV rescues the Di (2-ethylhexyl) phthalate (DEHP) induced oxidative stress in rat granulosa cells in vitro - Vivek Pandey; Alka Sharma; Sonal Tiwari; Yashvant Patel; Jayhind Kumar Chauhan; Safiya Ayesha; Alakh N. Sahu; Rashmi Gupta; Anima Tripathi; Pawan K. Dubey (Reproductive Toxicology, 2024)

Earthworms as Catalysts for Climate-Resilient Agriculture: Enhancing Food Security and Water Management in the Face of Climate Change - Muhammad Danish Toor; Abdul Basit; Benedict Okorie; Dibyajyoti Nath; Muhammad Mughees Ud Din; Pawan Kumar Verma; Saleem Sajjad; Izhar Ullah; Hany N. Yousef; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

Dissection of Physiological Traits for Terminal Heat Stress Tolerance in Indian Mustard (Brassica juncea L.) Using Microsatellite Markers - Raju Ram Choudhary; Ram Avtar; Pawan Kumar; Manjeet Singh; Mahavir Bishnoi; Neeraj Kumar; Rakesh Punia (Plant Molecular Biology Reporter, 2024)

In silico analysis and designing gRNA constructs for the precise modification of the OsTMS5 gene in rice (Oryza sativa L.): a comprehensive study and construct development for crop improvement - Laxmipreeya Behera; Kailash Ch. Samal; C. Parmeswaran; Pawan Kumar Agrawal; V. Mohan Murali Achary; Manasi Dash; Sanat Kumar Dwibedi; Raj Kumari Bhol; Bhagwat Singh Kherawat; Sang-Min Chung; Manzer H. Siddiqui; Saud Alamri; et al. (Cereal Research Communications, 2024)

Isolation of Monocrotophos degrading bacterial consortium from agricultural soil for in vivo analysis of pesticide degradation - Ramesh Kande; Karthik Rajkumar; Pawan Kumar Anoor; Srinivas Naik; Sandeepta Burgula (Brazilian Journal of Microbiology, 2024)

Drainage analysis of the Karanja River basin, Karnataka, India using Geo-informatics - Pawan Kumar Gautam (Applied Geomatics, 2024)

Forest fragmentation and forest cover dynamics: Mining induced changes in the West Singhbhum District of Jharkhand - Md Saharik Joy; Priyanka Jha; Pawan Kumar Yadav; Taruna Bansal; Pankaj Rawat; Shehnaz Begam (Remote Sensing Applications: Society and Environment, 2024)

Estimation of reservoir properties using pre-stack seismic inversion and neural network in mature oil field, Upper Assam basin, India - Pawan Kumar Singh; Uma Shankar (Journal of Applied Geophysics, 2024)

Grain size and sediment load control on channel migration patterns of the Ghaghara river from Faizabad to Deoria, Ganga plain, India - Pawan Kumar Gautam; Dhruv Sen Singh; Dhirendra Kumar; Anoop Kumar Singh (Arabian Journal of Geosciences, 2024)

Site selection for suitability of dam construction using analytic hierarchy process (AHP): A review study on rihand dam, uttar pradesh, india - Sushil Chandra; Pawan Kumar Gautam; Ajay Pratap Singh; Mohd. Ali Asgar Niazi (Arabian Journal of Geosciences, 2024)

Mix and manage: Cultivar mixtures can maintain yield under high wheat blast disease pressure - Timothy J. Krupnik; Md. Harun-Or-Rashid; Dinabandhu Pandit; Rabiul Islam; Md. Khaled Hossain; José Mauricio Cunha Fernandes; Krishna Kanta Roy; Muhammad Rezaul Kabir; Sabine Stuerz; Pawan Kumar Singh; Golam Faruq (Crop Protection, 2024)

Anti-tumor Effects of Polyphenols via Targeting Cancer Driving Signaling Pathways: A Review - Kareena Moar; Somu Yadav; Anuja Pant; Deepika; Pawan Kumar Maurya (Indian Journal of Clinical Biochemistry, 2024)

Interactions Between Microplastic and Heavy Metals in the Aquatic Environment: Implications for Toxicity and Mitigation Strategies - Nishita Narwal; Mian Adnan Kakakhel; Deeksha Katyal; Sangita Yadav; Pawan Kumar Rose; Eldon R. Rene; Md. Refat Jahan Rakib; Kuan Shiong Khoo; Navish Kataria (Water, Air, & Soil Pollution, 2024)

Characterizing urban flooding in the Kathmandu Valley, Nepal: the influence of urbanization and river encroachment - Anusha Danegulu; Saroj Karki; Pawan Kumar Bhattarai; Vishnu Prasad Pandey (Natural Hazards, 2024)

A Novel Rhodamine Probe Acting as Chemosensor for Selective Recognition of Cu2+ and Hg2+ Ions: An Experimental and First Principle Studies - Pawan Kumar Sada; Amit Bar; Amanpreet Kaur Jassal; Prabhat Kumar; S. Srikrishna; Alok Kumar Singh; Sumit Kumar; Laxman Singh; Abhishek Rai (Journal of Fluorescence, 2024)

Genomic, epigenomic and transcriptomic landscape of glioblastoma - Tikam Chand Dakal; Ganesh S. Kakde; Pawan Kumar Maurya (Metabolic Brain Disease, 2024)

Ecosystem health assessment of East Kolkata Wetlands, India: Implications for environmental sustainability - Pawan Kumar Yadav; Priyanka Jha; Md Saharik Joy; Taruna Bansal (Journal of Environmental Management, 2024)

Genetic association study of rs1801133 of MTHFR, rs4646903 of CYP1A1, null mutation of GSTM1&GSTT1 with leukemia in the Jammu region of north Indian population - Sushma Devi; Jyotdeep Kour Raina; Pawan Kumar; Amrit Sudershan; Ravi Sharma; Rakesh K. Panjalyia; Sanjeev K. Digra; Parvinder Kumar (The Nucleus, 2024)

Five Himalayan weeds as potential bioresources for bioactive agents: toxic compounds to valuable scaffolds - Ekta Bala; Varun Aggarwal; Pawan Kumar; Rohit Sharma; Saima; Manickam Selvaraj; Mohammed A. Assiri; Praveen Kumar Verma (Phytochemistry Reviews, 2024)

Engineering circular RNA for molecular and metabolic reprogramming - Narendra Kumar Sharma; Pragya Dwivedi; Ravi Bhushan; Pawan Kumar Maurya; Abhishek Kumar; Tikam Chand Dakal (Functional & Integrative Genomics, 2024)

An Efficient Protocol for Direct in vitro Regeneration in ‘Daisy’ and ‘W. Murcott’: Commercially Important Mandarins - Gurupkar Singh Sidhu; Davinder Kumar; Vishal Sharma; Jagveer Singh; Pawan Kumar Malhotra (Applied Fruit Science, 2024)

Performance of recycled concrete aggregates based self-compacting concrete containing coal combustion ashes and silica fume - Pawan Kumar; Navdeep Singh (European Journal of Environmental and Civil Engineering, 2024)

Biosynthesis of biomolecules from saffron as an industrial crop and their regulation, with emphasis on the chemistry, extraction methods, identification techniques, and potential applications in human health and food: A critical comprehensive review - Vishal Gupta; Gayatri Jamwal; Gyanendra Kumar Rai; Sushil Kumar Gupta; Rakesh Mohan Shukla; Basant Kumar Dadrwal; Pawan Prabhakar; Soubhagya Tripathy; Sudhir K. Rajpoot; Amit Kumar Singh; Deepak Kumar Verma; Gemilang Lara Utama; et al. (Biocatalysis and Agricultural Biotechnology, 2024)

Efficacy of Crude Extracts of Vitex negundo Against Helicoverpa armigera (Lepidoptera: Noctuidae) - Kamaldeep Singh Matharu; Pawan Kumar Mehta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Selection of reference genes for normalizing gene expression data across seasons in spermatozoa of water buffalo (Bubalus bubalis) - Rashi Vasisth; Ankita Gurao; Meenakshi Chitkara; Gautam Kumar; Karpenahalli Ranganatha Sriranga; Manishi Mukesh; Mahesh Shivanand Dige; Pawan Singh; Rajeev Anand Kumar Aggarwal; Ranjit Singh Kataria (International Journal of Biometeorology, 2024)

An approach towards different techniques for detection of heavy metal ions and their removal from waste water - Anoop Singh; Shahid Shafi Shah; Chandan Sharma; Vinay Gupta; Ashok K. Sundramoorthy; Pawan Kumar; Sandeep Arya (Journal of Environmental Chemical Engineering, 2024)

Food waste to hydrochar: A potential approach towards the Sustainable Development Goals, carbon neutrality, and circular economy - Sanju Bala Dhull; Pawan Kumar Rose; Jyoti Rani; Gulden Goksen; Aarti Bains (Chemical Engineering Journal, 2024)

A Multivariate Geomorphometric Approach to Prioritize Drought Prone Sakri Basin for Land and Water Resource Management - Pawan Jeet; Anil Kumar Singh; Ashutosh Upadhyaya; Anup Das; Rakesh Kumar; Prem Kumar Sundaram; Arti Kumari; Kirti Saurabh; Deepak Singh; Prem Pal Kumar (Journal of the Indian Society of Remote Sensing, 2024)

Ultrasonication-assisted synthesis of transition metal carbide of MXene: an efficient and promising material for photocatalytic organic dyes degradation of rhodamine B and methylene blue in wastewater - Gautam Kumar; Amit Ahlawat; Hema Bhardwaj; Gaurav Kumar Sahu; Pawan S. Rana; Partima R. Solanki (Environmental Science and Pollution Research, 2024)

Physicochemical characterization of rice straw before and after alkali-assist photocatalytic pretreatment: a comparative analysis - Nisha Sethi; Neha Luhach; Anita Singh Kirrolia; Asha Gupta; Narsi Ram Bishnoi; Sanju Bala Dhull; Pawan Kumar Rose (Environmental Science and Pollution Research, 2024)

Fused Deposition Modeling 3D-Printed Scaffolds for Bone Tissue Engineering Applications: A Review - Pawan Kumar; Shamim; Mohammad Muztaba; Tarmeen Ali; Jyoti Bala; Haramritpal Singh Sidhu; Amit Bhatia (Annals of Biomedical Engineering, 2024)

Isocratic elution based analytical method for quantification of phytoconstituents in Hedychium spicatum and evaluation of their α-glucosidase inhibitory activity - Antim K. Maurya; Pawan Kumar; Vijai K. Agnihotri (Natural Product Research, 2024)

Biopesticides: Uses and importance in insect pest control: A review - Babu Saddam; Muhammad Aqib Idrees; Pawan Kumar; Mohammad Mahamood (International Journal of Tropical Insect Science, 2024)

Abrupt intensification of AMOC and monsoonal winds during mid-MIS4 (Heinrich Event 6) in the western Arabian Sea - Hidayatullah Khan; Pawan Govil; Rajani Panchang; Shailesh Agrawal; Pankaj Kumar; Brijesh Kumar; Divya Verma (Global and Planetary Change, 2024)

Spatial assessment of flood vulnerability and waterlogging extent in agricultural lands using RS-GIS and AHP technique—a case study of Patan district Gujarat, India - Nitin Surendra Singh Gahalod; Kumar Rajeev; Pawan Kumar Pant; Sonam Binjola; Rameshwar Lal Yadav; Rang Lal Meena (Environmental Monitoring and Assessment, 2024)

Phosphorus distribution in the water and sediments of the Ganga and Yamuna Rivers, Uttar Pradesh, India: insights into pollution sources, bioavailability, and eutrophication implications - Kriti Varma; Pawan Kumar Jha (Environmental Monitoring and Assessment, 2024)

Circulating miRNA-21 Levels in Breast Cancer Patients Before and After Chemotherapy and Its Association with Clinical Improvement - Sanchi Sukhija; Purvi Purohit; Puneet Pareek; Pawan Kumar Garg; Jeewan Ram Vishnoi; Poonam Abhay Elhence; Shobhan Babu Varthya; Praveen Sharma; Sneha Ambwani; Jaykaran Charan (Indian Journal of Clinical Biochemistry, 2024)

Statistical downscaling of maximum temperature under CMIP6 global climate models and evaluation of heat wave events using deep learning methods for Indo‐Gangetic Plain - Manisha Chaturvedi; Rajesh Kumar Mall; Saumya Singh; Pawan K. Chaubey; Ankur Pandey (International Journal of Climatology, 2024)
The rising global temperature is one of the primary concerns of the world as it impacts the economy, environment and healthcare of any country which are more pronounced a regional level. Assessment of regional impacts of climate change at a local level requires fine resolution of climate data for which a robust and fast downscaling method is needed. In this study, we use three deep learning‐based methods, namely long short‐term memory network (LSTM), deep neural network (DNN) and recurrent neural network (RNN), to downscale CMIP6 13 GCMS models data (1.25° × 1.25° resolution) global climate model (GCM) maximum temperature (Tmax) at a regional scale of 0.5° × 0.5° spatial resolution for the period 1991–2010 over the Indo‐Gangetic Plain (IGP). In addition to the temperature prediction, heat wave events have been also analysed in the study. The study found that LSTM method performs better than DNN and RNN in downscaling of all GCM model datasets when evaluated against observed maximum temperature data from the India Meteorological Department (IMD) in terms of RMSE (0.9–3.5), average of all grid MAE value between (1.2 and 2.68), correlation (0.68–0.9) along with and spatiotemporal variability. LSTM also performed better in heat wave prediction over the region with similar temporal range (12–36 events) and spatial occurrence as compared to the observation (12–28 events). Overall, the study concludes that LSTM performs better than two methods for Indo‐Gangetic Plain with best hyper parameter tuning. Hence, we propose to utilize a deep learning framework based on LSTM for downscaling GCM dataset at a finer resolution.

Occurrence, transport, and toxicity of microplastics in tropical food chains: perspectives view and way forward - Navish Kataria; Sangita Yadav; Vinod Kumar Garg; Eldon R. Rene; Jheng-Jie Jiang; Pawan Kumar Rose; Mukesh Kumar; Kuan Shiong Khoo (Environmental Geochemistry and Health, 2024)

Estimation of flood inundation in river basins of Uttar Pradesh using Sentinel 1A-SAR data on Sentinel Application Platform (SNAP) - Pawan Kumar Gautam; Sushil Chandra; Pradnita Komal Henry (Arabian Journal of Geosciences, 2024)

Sustainable utilization of sewage sludge ash in stabilizing subgrade soil: an appraisal - Pawan Kishor Sah; Bikash Kumar Sah; Shiv Shankar Kumar (Environment, Development and Sustainability, 2024)

Exploring the use of supercritical carbon dioxide in enzymatic hydrolysis of cellulosic substrate - Pawan Kumar; Azadeh Kermanshahi pour; Satinder Kaur Brar; Charles Chunbao Xu (Bioresource Technology Reports, 2024)

In vitro and In silico evaluation of the antioxidant, anti-microbial and antihyperglycemic properties of giloy (Tinospora cordifolia L.) stem extract - Kimmy; Deepak Kumar Verma; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Pradyuman Kumar; Prem Prakash Srivastav; Mamoni Banerjee (Biocatalysis and Agricultural Biotechnology, 2024)

AFB1 induced free radicals cause encephalopathy in goat kids via intrinsic pathway of apoptosis: pathological and immunohistochemical confirmation of non-hepatic neuroaflatoxicosis - Monalisa Sahoo; Jigarji Chaturji Thakor; Pradeep Kumar; Rajendra Singh; Pawan Kumar; Karampal Singh; Bhavani Puvvala; Ajay Kumar; Aswathy Gopinathan; Santwana Palai; Sushmita Patra; Jagannath Prasad Tripathy; et al. (Veterinary Research Communications, 2024)

A novel approach using ATR-FTIR spectroscopy and chemometric analysis to distinguish male and female human hair samples - Sukriti Thakur; Akanksha Sharma; Rafał Cieśla; Pawan Kumar Mishra; Vishal Sharma (The Science of Nature, 2024)

Monitoring forest cover changes and its impact on land surface temperature using geospatial technique in Talra Wildlife Sanctuary, Shimla, India - Pawan Kumar Thakur; Sher Singh Samant; Raj Kumar Verma; Atul Saini; Monika Chauhan (Environment, Development and Sustainability, 2024)

Split application of gibberellins at different growth stages to improve the yield and quality of cape gooseberry (Physalis peruviana L.) under subtropical plain - Madhvendra Bahadur Singh; Pawan Kumar; Manoj Kundu; Samik Sengupta; Kuldeep (Vegetos, 2024)

Investigation of conical passive solar still by incorporating energy metrics, efficiency, and sensitivity analyses for sustainable solar distillation - Gajendra Singh; Pawan Kumar Singh; Abhishek Saxena; Navneet Kumar; Desh Bandhu Singh (Journal of Cleaner Production, 2024)

Effect of addition of methionine and histidine on physicochemical and rheological characteristics of water chestnut starch as revealed by molecular dynamic simulations - Sonia Attri; Baljeet S. Yadav; Ritika B.Yadav; Ajit Kumar; Pawan Kumar (Food Research International, 2024)

Response surface bioprocess provenance for enhanced chitinase production by Thermomyces dupontii for translation of chitinous waste to short-chain chitooligosaccharides - Rajni Kumari; Manish Kumar; Apoorva Upadhayay; Pawan K. Dadheech; V. Vivekanand; Nidhi Pareek (Biocatalysis and Agricultural Biotechnology, 2024)

Minor millets based agroforestry of multipurpose tree species of Bhimal (Grewia optiva Drummond J.R. ex Burret) and Mulberry (Morus alba L.) for resource conservation and production in north western Himalayas – 10-year study - Harsh Mehta; A.C. Rathore; J.M.S. Tomar; D. Mandal; Pawan Kumar; Suresh Kumar; S.K. Sharma; Rajesh Kaushal; Charan Singh; O.P. Chaturvedi; M. Madhu (Agriculture, Ecosystems & Environment, 2024)

SFM_MB Toolbox: a new ArcGIS toolbox for building spatial distribution maps of soil fertility using model builder in ArcMap of ArcGIS, a case study - Ranga Rao Velamala; Pawan Kumar Pant (Arabian Journal of Geosciences, 2024)

Production of renewable fuels by the photocatalytic reduction of CO2 using magnesium doped natural ilmenite - Diana M. Cañas-Martínez; Pawan Kumar; Juvencio Vazquez-Samperio; Md Golam Kibria; Julio A. Pedraza-Avella (Journal of Environmental Chemical Engineering, 2023)

Quality by design–based development and optimization of fourth-generation ternary solid dispersion of standardized Piper longum extract for melanoma therapy - Debadatta Mohapatra; Dulla Naveen Kumar; Singh Shreya; Vivek Pandey; Pawan K. Dubey; Ashish Kumar Agrawal; Alakh N Sahu (Drug Delivery and Translational Research, 2023)

Projected trends in hydro-climatic extremes in small-to-mid-sized watersheds in eastern Nepal based on CMIP6 outputs - Aman Shrestha; Buddha Subedi; Bishal Shrestha; Ajeeta Shrestha; Angel Maharjan; Pawan Kumar Bhattarai; Vishnu Prasad Pandey (Climate Dynamics, 2023)

Forecasting global plastic production and microplastic emission using advanced optimised discrete grey model - Subhra Rajat Balabantaray; Pawan Kumar Singh; Alok Kumar Pandey; Bhartendu Kumar Chaturvedi; Aditya Kumar Sharma (Environmental Science and Pollution Research, 2023)

Emerging micropollutants in aquatic ecosystems and nanotechnology-based removal alternatives: A review - Nishita Narwal; Deeksha Katyal; Navish Kataria; Pawan Kumar Rose; Sudhir Gopalrao Warkar; Arivalagan Pugazhendhi; Suresh Ghotekar; Kuan Shiong Khoo (Chemosphere, 2023)

Congo red dye removal using modified banana leaves: Adsorption equilibrium, kinetics, and reusability analysis - Pawan Kumar Rose; Vikash Poonia; Rakesh Kumar; Navish Kataria; Prabhakar Sharma; Jasmeet Lamba; Prosun Bhattacharya (Groundwater for Sustainable Development, 2023)

Wedge and side grafting: a boon for mass multiplication of jackfruit (Artocarpus hetrophylus L.) plants under subtropical humid condition - Kuldeep; Manoj Kundu; Hidayatullah Mir; Pawan Kumar; Shubranil Das (Vegetos, 2023)

Rice husk biochar - A novel engineered bio-based material for transforming groundwater-mediated fluoride cycling in natural environments - Rakesh Kumar; Prabhakar Sharma; Pushpa Kumari Sharma; Pawan Kumar Rose; Rakesh Kumar Singh; Nishant Kumar; Prafulla Kumar Sahoo; Jyoti Prakash Maity; Ashok Ghosh; Manish Kumar; Prosun Bhattacharya; Ashok Pandey (Journal of Environmental Management, 2023)

Bioinspired multimetal electrocatalyst for selective methane oxidation - Tareq Al-Attas; M.A. Khan; Tiago J. Goncalves; Nael G. Yasri; Soumyabrata Roy; Ali Shayesteh Zeraati; Pawan Kumar; Kristen A. Miller; Pulickel M. Ajayan; Ian D. Gates; Jinguang Hu; Venkataraman Thangadurai; et al. (Chemical Engineering Journal, 2023)

Genetic analysis for semen quality traits in buffalo bulls - Devender Kumar; J. S. Mehta; A. Jerome; Pradeep Kumar; D. Kumar; B Shivani; C. S. Patil; Renu Bala; Nisha Verma; Satish Nain; R. K. Sharma; Pawan Singh (Tropical Animal Health and Production, 2023)

Heterologous expression and characterization of ToxA1 haplotype from India and its interaction with Tsn1 for spot blotch susceptibility in spring wheat - Ranjan Kumar Chaubey; Dharamsheela Thakur; Sudhir Navathe; Sandeep Sharma; Vinod Kumar Mishra; Pawan Kumar Singh; Ramesh Chand (Molecular Biology Reports, 2023)

Coinfection of porcine astrovirus and other porcine viruses in diarrheic pigs in Haryana, India - Vaishali; Renu Gupta; Mohit Kumar; Nitish Bansal; Vivek; Parveen Kumar; Pawan Kumar; Naresh Jindal (Archives of Virology, 2023)

Exergo-enviro-economic and yearly productivity analyses of conical passive solar still for sustainable solar distillation - Gajendra Singh; Pawan Kumar Singh; Abhishek Saxena; Ritvik Dobriyal; Navneet Kumar; Desh Bandhu Singh (Environmental Science and Pollution Research, 2023)

Geochemistry of an intercalated unit of arkose and shale of the Dhandraul Formation belonging to the Vindhyan Supergroup, Eastern India: Insights from provenance, depositional environment, and geodynamic set-up - Pawan Kumar Yadav; Manorama Das (Journal of Sedimentary Environments, 2023)

Optical Sensing Capability Evaluation for Methylammonium Based Perovskites for Explosive - Rajat Sikka; Pawan Kumar (Journal of Fluorescence, 2023)

Characterization of Foot-and-Mouth Disease Virus Serotype O-Specific Single Domain Antibody Expressed in the pET Expression System - Vijay Kumar; Swati Dahiya; Savita Budania; Akhil Kumar Gupta; Punesh Sangwan; Anshul Lather; Pawan Kumar; Naresh Kumar Kakker; Ajit Singh (Indian Journal of Microbiology, 2023)

Application of Hybrid ANN Techniques for Drought Forecasting in the Semi-Arid Region of India - Pawan S. Wable; Madan Kumar Jha; Sirisha Adamala; Mukesh Kumar Tiwari; Sabinaya Biswal (Environmental Monitoring and Assessment, 2023)

Chromite chemistry as petrogenetic indicator of altered ultramafic rocks from Higher Himalayan Crystalline, Kishtwar, India - Pawan Singh; Pankaj Kumar Srivastava (Journal of Earth System Science, 2023)

Prediction of heterotic combinations using correlation between genetic distance, heterosis and combining ability in yellow sarson (Brassica rapa var. yellow sarson Prain) - Sanchika Snehi; Nitish Ranjan Prakash; Usha Pant; Pawan Kumar Singh; Santosh Kumar; Anand Singh Jeena; Ram Bhajan (Vegetos, 2023)

Modeling flood susceptibility zones using hybrid machine learning models of an agricultural dominant landscape of India - Satish Kumar Saini; Susanta Mahato; Deep Narayan Pandey; Pawan Kumar Joshi (Environmental Science and Pollution Research, 2023)

Assessment of hydrochemical shift in riverine aquifers of the mid-Gangetic plain of Uttar Pradesh, India - Piyush Tripathi; Manish Kumar; Chandrashekhar Bhagat; Pawan Kumar Jha (Groundwater for Sustainable Development, 2023)

Optimization of MAE for Carica papaya phytochemicals, and its in silico, in vitro, and ex vivo evaluation: For functional food and drug applications - Pawan Prabhakar; Sayan Mukherjee; Ankit Kumar; Suraj Kumar; Deepak Kumar Verma; Santanu Dhara; Mrinal Kumar Maiti; Mamoni Banerjee (Food Bioscience, 2023)

Global co-occurrences of multi-(emerging)-contaminants in the hotspots of arsenic polluted groundwater: A pattern of menace - Manish Kumar; Nilotpal Das; Sachin Tripathi; Atul Verma; Pawan Kumar Jha; Prosun Bhattacharya; Jürgen Mahlknecht (Current Opinion in Environmental Science & Health, 2023)

Development and validation of most efficient RNA isolation method from buffalo bull spermatozoa - Rashi Vasisth; Ankita Gurao; Namita Kumari; Gautam Kumar; Anurag Kumar; Karpenahalli Ranganatha Sriranga; Mahesh Shivanand Dige; Manishi Mukesh; Rajeev Anand Kumar Aggarwal; Pawan Singh; Ranjit Singh Kataria (Molecular Biology Reports, 2023)

Surface and thermocline ocean circulation intensity changes in the western Arabian Sea during ∼172 kyr - Hidayatullah Khan; Pawan Govil; Rajani Panchang; Shailesh Agrawal; Pankaj Kumar; Brijesh Kumar; Divya Verma (Quaternary Science Reviews, 2023)

Assessment of different carrier materials for the preparation of microbial formulations to enhance the shelf life and its efficacy on the growth of spinach (Spinacia oleracea L.) - Nazia Parveen; Roli Mishra; Dig Vijay Singh; Pawan Kumar; Rana Pratap Singh (World Journal of Microbiology and Biotechnology, 2023)

A dual channel rhodamine appended smart probe for selective recognition of Cu2+ and Hg2+ via “turn on” optical readout - Pawan Kumar Sada; Amit Bar; Amanpreet Kaur Jassal; Alok Kumar Singh; Laxman Singh; Abhishek Rai (Analytica Chimica Acta, 2023)

Recent analytical techniques, and potential eco-toxicological impacts of textile fibrous microplastics (FMPs) and associated contaminates: A review - Sangita Yadav; Navish Kataria; Pradeep Khyalia; Pawan Kumar Rose; Santanu Mukherjee; Himani Sabherwal; Wai Siong Chai; Saravanan Rajendran; Jheng-Jie Jiang; Kuan Shiong Khoo (Chemosphere, 2023)

Simple isocratic RP-UHPLC-MS methods for the determination of steviols and its glycosides: Quality control perspectives - Pawan Kumar; Dinesh Kumar; Vivek Yadav; Sushil K. Maurya; Rajiv K. Tonk; Dinesh Kumar (Food Bioscience, 2023)

An evaluation of the three-component pubic symphyseal human age estimation method: a CT-based exploration in an Indian population - Varsha Warrier; Rutwik Shedge; Pawan Kumar Garg; Shilpi Gupta Dixit; Kewal Krishan; Tanuj Kanchan (The Science of Nature, 2023)

Drinking water quality status from source to consumer: a study for Ashti town in Wardha District of Maharashtra, India - Gajanan K. Khadse; Mahesh Kumar; Pawan K. Labhasetwar (Sustainable Water Resources Management, 2023)

Insights into Changing Dermatophyte Spectrum in India Through Analysis of Cumulative 161,245 Cases Between 1939 and 2021 - Pawan Kumar; S. Ramachandran; Shukla Das; S. N. Bhattacharya; Bhupesh Taneja (Mycopathologia, 2023)
Dermatophytosis is one of the most common superficial infections of the skin affecting nearly one-fifth of the world population at any given time. With nearly 30% of worldwide terbinafine-resistance cases in Trichophyton mentagrophytes/Trichophyton interdigitale and Trichophyton rubrum reported from India in recent years, there is a significant burden of the emerging drug resistance epidemic on India. Here, we carry out a comprehensive retrospective analysis of dermatophytosis in India using 1038 research articles pertaining to 161,245 cases reported from 1939 to 2021. We find that dermatophytosis is prevalent in all parts of the country despite variable climatic conditions in different regions. Our results show T. rubrum as the most prevalent until 2015, with a sudden change in dermatophyte spectrum towards T. mentagrophytes / T. interdigitale complex since then. We also carried out an 18S rRNA-based phylogenetics and an average nucleotide identity-and single nucleotide polymorphism-based analysis of available whole genomes and find very high relatedness among the prevalent dermatophytes, suggesting geographic specificity. The comprehensive epidemiological and phylogenomics analysis of dermatophytosis in India over the last 80 years, presented here, would help in region-specific prevention, control and treatment of dermatophyte infections, especially considering the large number of emerging resistance cases.

Genotypes with high stem reserve mobilization can overcome the impact of rust on chickpea yield - Pawan Kumar Mohanty; R. Shiv Ramakrishnan; B. C. Mamatha; K. Rudresh; P. R. Sabale; Madan Pal; R. K. Samaiya; J. Rane; S. Gurumurthy (Genetic Resources and Crop Evolution, 2023)

A multi-model forecasting approach for solid waste generation by integrating demographic and socioeconomic factors: a case study of Prayagraj, India - Atul Srivastava; Pawan Kumar Jha (Environmental Monitoring and Assessment, 2023)

Geochemical characterization of tourmaline from granitic pegmatites, Higher Himalayan Crystalline (HHC), Paddar area, India - Pawan Singh; Pankaj Kumar Srivastava (Arabian Journal of Geosciences, 2023)

Assessment of potentially toxic elements in groundwater through interpolation, pollution indices, and chemometric techniques in Dehradun in Uttarakhand State - Anjali Nayak; Gagan Matta; Devi Prasad Uniyal; Avinash Kumar; Pawan Kumar; Gaurav Pant (Environmental Science and Pollution Research, 2023)

Congo red dye adsorption onto cationic amino-modified walnut shell: Characterization, RSM optimization, isotherms, kinetics, and mechanism studies - Pawan Kumar Rose; Rajat Kumar; Rakesh Kumar; Manish Kumar; Prabhakar Sharma (Groundwater for Sustainable Development, 2023)

Molecular characterization of soybean yellow mosaic virus isolates and identification of stable resistance sources in central India - Pawan K. Amrate; M. K. Shrivastava; Munmi Borah; Gowtham Kumar Routhu; Stuti Sharma; Vennampally Nataraj; Dinesh K. Pancheshwar; Gyanendra Singh (Australasian Plant Pathology, 2023)

Identification of environmental stress parameters to study the natural colour change of water in highly saline inland Crater Lake at Lonar, India - Atul Maldhure; Anupama Rodge; Anjali Kothe; Pranav Nagarnaik; Gajanan Khadse; Amit Bafana; Mahesh Kumar; Pawan Labhasetwar (Environmental Monitoring and Assessment, 2023)

Drinking water treatment and associated toxic byproducts: Concurrence and urgence - Manish Kumar; Shashank Shekhar; Rakesh Kumar; Pawan Kumar; Muthusamy Govarthanan; Tushara Chaminda (Environmental Pollution, 2023)

Projected changes in hydro-climatic extremes with CMIP6 climate model outputs: a case of rain-fed river systems in Western Nepal - Tek Narayan Bhattarai; Swastik Ghimire; Saugat Aryal; Yubin Baaniya; Saurav Bhattarai; Shraddha Sharma; Pawan Kumar Bhattarai; Vishnu Prasad Pandey (Stochastic Environmental Research and Risk Assessment, 2023)

Phenomenal Preservations of Stromatolites in Bilara Group of Marwar Supergroup, Western India: Implication for Establishment as Geosites - V. S. Parihar; Hukmaram; Pawan Kumar; Anshul Harsh (Geoheritage, 2023)

Changes in physicochemical, heavy metals and air quality linked to spot Aplocheilus panchax along Mahanadi industrial belt of India under COVID-19-induced lockdowns - Biswaranjan Paital; Samar Gourav Pati; Falguni Panda; Sujit Kumar Jally; Pawan Kumar Agrawal (Environmental Geochemistry and Health, 2023)

Hydrogeochemical facie and solute acquisition at Dal Lake of Kashmir and Dal Lake of Mcleodganj, northwest Himalaya, India - Pawan Kumar; Ambrish Kumar Mahajan (Journal of Earth System Science, 2023)

Facile synthesis of carbon dots via pyrolysis and their application in photocatalytic degradation of rhodamine B (RhB) - Amit Ahlawat; Tarun Kumar Dhiman; Pratima R. Solanki; Pawan S. Rana (Environmental Science and Pollution Research, 2023)

Microplastics in multimedia environment: A systematic review on its fate, transport, quantification, health risk, and remedial measures - Pawan Kumar Rose; Monika Jain; Navish Kataria; Prafulla Kumar Sahoo; Vinod Kumar Garg; Anoop Yadav (Groundwater for Sustainable Development, 2023)

Novel benzenesulfonamide bearing 1,2,4-triazoles as potent anti-microbial and anti-oxidant agents - Chander; Monika; Akhilesh Kumar; Deepansh Sharma; Pawan K. Sharma; Sita Ram (Medicinal Chemistry Research, 2023)

Prediction of surface temperature and CO2 emission of leading emitters using grey model EGM (1,1, α, θ) - Pawan Kumar Singh; Alok Kumar Pandey; Anushka Chouhan; Gopal Ji Singh (Environmental Science and Pollution Research, 2023)

Forecasting of non-renewable and renewable energy production in India using optimized discrete grey model - Alok Kumar Pandey; Pawan Kumar Singh; Muhammad Nawaz; Amrendra Kumar Kushwaha (Environmental Science and Pollution Research, 2023)

Impact of Chronic Sodium Fluoride Toxicity on Antioxidant Capacity, Biochemical Parameters, and Histomorphology in Cardiac, Hepatic, and Renal Tissues of Wistar Rats - Priyanka Sharma; Pawan Kumar Verma; Shilpa Sood; Maninder Singh; Deepika Verma (Biological Trace Element Research, 2023)

Geology, petrology, and geochemistry of the Mesoproterozoic Kaimur Group of rocks of the Vindhyan Supergroup, Eastern India: implications for depositional environment and sequence stratigraphy - Pawan Kumar Yadav; Manorama Das; Sukhendu Ray (Journal of Sedimentary Environments, 2022)

Genomic selection for spot blotch in bread wheat breeding panels, full-sibs and half-sibs and index-based selection for spot blotch, heading and plant height - Philomin Juliana; Xinyao He; Jesse Poland; Krishna K. Roy; Paritosh K. Malaker; Vinod K. Mishra; Ramesh Chand; Sandesh Shrestha; Uttam Kumar; Chandan Roy; Navin C. Gahtyari; Arun K. Joshi; et al. (Theoretical and Applied Genetics, 2022)
Key message Genomic selection is a promising tool to select for spot blotch resistance and index-based selection can simultaneously select for spot blotch resistance, heading and plant height. Abstract A major biotic stress challenging bread wheat production in regions characterized by humid and warm weather is spot blotch caused by the fungus Bipolaris sorokiniana . Since genomic selection (GS) is a promising selection tool, we evaluated its potential for spot blotch in seven breeding panels comprising 6736 advanced lines from the International Maize and Wheat Improvement Center. Our results indicated moderately high mean genomic prediction accuracies of 0.53 and 0.40 within and across breeding panels, respectively which were on average 177.6% and 60.4% higher than the mean accuracies from fixed effects models using selected spot blotch loci. Genomic prediction was also evaluated in full-sibs and half-sibs panels and sibs were predicted with the highest mean accuracy (0.63) from a composite training population with random full-sibs and half-sibs. The mean accuracies when full-sibs were predicted from other full-sibs within families and when full-sibs panels were predicted from other half-sibs panels were 0.47 and 0.44, respectively. Comparison of GS with phenotypic selection (PS) of the top 10% of resistant lines suggested that GS could be an ideal tool to discard susceptible lines, as greater than 90% of the susceptible lines discarded by PS were also discarded by GS. We have also reported the evaluation of selection indices to simultaneously select non-late and non-tall genotypes with low spot blotch phenotypic values and genomic-estimated breeding values. Overall, this study demonstrates the potential of integrating GS and index-based selection for improving spot blotch resistance in bread wheat.

Characteristics of Pooled Wharton’s Jelly Mesenchymal Stromal Cells (WJ-MSCs) and their Potential Role in Rheumatoid Arthritis Treatment - Suresh Kannan; Pachaiyappan Viswanathan; Pawan Kumar Gupta; Uday Kumar Kolkundkar (Stem Cell Reviews and Reports, 2022)

Propagation through juvenile shoot cuttings in difficult-to-root Dalbergia latifolia – examining role of endogenous IAA in adventitious rooting - Pramod Kumar; Pawan Kumar Patel; M. K. Sonkar (Plant Physiology Reports, 2022)

Comparative transcriptome profiling of Polianthes tuberosa during a compatible interaction with root-knot nematode Meloidogyne incognita - Kanchan B M Singh; Pawan Jayaswal; Shivani Chandra; Jayanthi M.; Pranab Kumar Mandal (Molecular Biology Reports, 2022)

Fungal consortium and nitrogen supplementation stimulates soil microbial communities to accelerate in situ degradation of paddy straw - Ajay Kumar; Surender Singh; Pawan Kumar; Yashbir Singh Shivay; Shrila Das; Madan Pal; Niveta Jain; Lata Nain (Environmental Sustainability, 2022)

Surface hydrographic variations in the western Arabian Sea through the last 172 kyr - Hidayatullah Khan; Pawan Govil; Rajani Panchang; Pankaj Kumar; Shailesh Agrawal (Geo-Marine Letters, 2022)

Correction to: Four New Species of the Genus Pallisentis (Quadrigyridae, Van Cleave, 1920) from Freshwater Fish in Uttar Pradesh, India - Neelam Kumari Gautam; Pawan Kumar Misra; Anand Murai Saxena (Acta Parasitologica, 2022)

Sustainable adsorptive removal of antibiotics from aqueous streams using Fe3O4-functionalized MIL101(Fe) chitosan composite beads - Pratibha Yadav; Anshul Yadav; Pawan Kumar Labhasetwar (Environmental Science and Pollution Research, 2022)

Dose-Dependent Oxidative Damage in Erythrocytes and Hepatic Tissue of Wistar Rats Concurrently Exposed with Arsenic and Quinalphos: a Subacute Study - Pawan Kumar Verma; Parvinder Singh; Priyanka Sharma; Shilpa Sood; Rajinder Raina (Biological Trace Element Research, 2022)

Effect of biostimulation on growth rate and reproductive development of Bos indicus dairy heifers - Sanjay Choudhary; M.L. Kamboj; Dharma Sahu; Sunil Dutt; Ankit Magotra; Pawan Singh; Nishant Kumar; Rodolfo Ungerfeld; C Kotresh Prasad (Tropical Animal Health and Production, 2022)

Multiple forecasting approach: a prediction of CO2 emission from the paddy crop in India - Pawan Kumar Singh; Alok Kumar Pandey; Sahil Ahuja; Ravi Kiran (Environmental Science and Pollution Research, 2022)

Chikungunya Virus Vaccine Development: Through Computational Proteome Exploration for Finding of HLA and cTAP Binding Novel Epitopes as Vaccine Candidates - Priti Sharma; Pawan Sharma; Sheeba Ahmad; Ajay Kumar (International Journal of Peptide Research and Therapeutics, 2022)

Reaction of Algerian and international germplasm of wheat against races 1 and 5 of Pyrenophora tritici-repentis the causal agent of tan spot - Noureddine Ouaar; Abdelkader Benbelkacem; Pawan Kumar Singh; Sabrina Oumata; Hamida Benslimane (Cereal Research Communications, 2022)

Genetic diversity and population structure analysis for morphological traits in upland cotton (Gossypium hirsutum L.) - Pawan Kumar; Somveer Nimbal; Neeraj Budhlakoti; Varsha Singh; Rajvir Singh Sangwan (Journal of Applied Genetics, 2022)

Potent γ-amino butyric acid producing psychobiotic Lactococcus lactis LP-68 from non-rhizospheric soil of Syzygium cumini (Black plum) - Pushpendra Sharma; Neera Singh; Surender Singh; Sunil Kumar Khare; Pawan Kumar Singh Nain; Lata Nain (Archives of Microbiology, 2022)

Quercetin Mitigates Red Blood Cell Membrane Bound Na+, K+-ATPase Transporter During Human Aging - Akshay Kumar; Pawan Kumar Maurya (The Journal of Membrane Biology, 2021)

Effect of foam insertion in aneurysm sac on flow structures in parent lumen: relating vortex structures with disturbed shear - Pawan Kumar Pandey; Malay Kumar Das (Physical and Engineering Sciences in Medicine, 2021)

Evaluation of site-specific characteristics using microtremor measurements in the Gorakhpur city of Uttar Pradesh, India - Uma Shankar; Pawan Kumar Yadav; A P Singh; Arun Kumar Gupta (Journal of Earth System Science, 2021)

Effects of piperazine and EDTA in garden snail towards electrolytic variation and antimicrobial activities - Anil Kumar; Varun Dhiman; Pawan Kumar; Deepak Pant (Environmental Science and Pollution Research, 2021)

Quantifying monthly water balance to estimate water deficit in Mayurakshi River basin of Eastern India - Swades Pal; Susanta Mahato; Biplab Giri; Deep Narayan Pandey; Pawan Kumar Joshi (Environment, Development and Sustainability, 2021)

Geochemistry of metasedimentary clastic rocks from Dhanjori and Badampahar Groups, Singhbhum Craton, Eastern India: implications for tectonic setting and Archean–Proterozoic boundary - Pawan Kumar Yadav; Manorama Das (Journal of Sedimentary Environments, 2021)

Generation of polyclonal antibodies against recombinant Agrobacterium tumefaciens decaprenyl diphosphate synthase produced in Escherichia coli - Honey Yadav; Kapil Malik; Sanjay Parmar; Shashi Kumar; Pawan K. Jaiwal (Journal of Plant Biochemistry and Biotechnology, 2021)

Variability in alkaloid and phenolic content vis-a-vis antigout potential among the natural population of Gloriosa superba (L.) collected from Central India - Ankita Misra; Sharad Srivastava; Pushpendra Kumar Shukla; Manish Kumar; Md. Khalid; Poonam Kushwaha; Pawan Kumar Agrawal (Natural Product Research, 2021)

Evaluation of elite bread wheat lines for resistance to blast disease in Bangladesh - Krishna Kanta Roy; Md Mostofa Ali Reza; Md Muzahid-E-Rahman; Md Babul Anwar; Kishowar-E-Mustarin; Muhammad Rezaul Kabir; Paritosh Kumar Malaker; Naresh Chandra Deb Barma; Md Israil Hossain; Xinyao He; Aakash Chawade; Pawan Kumar Singh (Euphytica, 2021)

Top Down Computational Approach: A Vaccine Development Step to Find Novel Superantigenic HLA Binding Epitopes from Dengue Virus Proteome - Priti Sharma; Pawan Sharma; Sheeba; Ajay Kumar (International Journal of Peptide Research and Therapeutics, 2021)

Effect of moulding water content on strength characteristics of a cement-stabilized granular lateritic soil - Pawan Kumar Chamling; Dipti Ranjan Biswal; Umesh Chandra Sahoo (Innovative Infrastructure Solutions, 2021)

Effect of various hCG treatment protocols on luteal characteristics, plasma progesterone concentration, and pregnancy in normal cyclic Indian crossbred dairy cows - Sanjay Agarwal; Harihar Prasad Gupta; Shiv Prasad; Pawan Kumar Verma; Afroza Khanam; Firdous Ahmad Khan (Tropical Animal Health and Production, 2021)

Molecular characterization of SlATG18f in response to Tomato leaf curl New Delhi virus infection in tomato and development of a CAPS marker for leaf curl disease tolerance - Ashish Prasad; Gunaseelen Hari-Gowthem; Mehanathan Muthamilarasan; Zakir Hussain; Pawan Kumar Yadav; Sandhya Tripathi; Manoj Prasad (Theoretical and Applied Genetics, 2021)

First report of barley blast caused by Magnaporthe oryzae pathotype Triticum (MoT) in Bangladesh - Krishna Kanta Roy; Md Mostofa Ali Reza; Md Muzahid-E-Rahman; Kishowar E. Mustarin; Paritosh Kumar Malaker; Naresh Chandra Deb Barma; Xinyao He; Pawan Kumar Singh (Journal of General Plant Pathology, 2021)

Near-surface seismic site characterization using Nakamura-based HVSR technique in the geological complex region of Kangra Valley, northwest Himalaya, India - Ambrish Kumar Mahajan; Praveen Kumar; Pawan Kumar (Arabian Journal of Geosciences, 2021)

A multinomial logistic model-based land use and land cover classification for the South Asian Association for Regional Cooperation nations using Moderate Resolution Imaging Spectroradiometer product - Ram Kumar Singh; Vinay Shankar Prasad Sinha; Pawan Kumar Joshi; Manoj Kumar (Environment, Development and Sustainability, 2021)

Efficacy and Safety of New and Emerging Drugs for COVID-19: Favipiravir and Dexamethasone - Shivani Sood; Gurpreet Kaur Bhatia; Prachi Seth; Pawan Kumar; Jagjit Kaur; Vidisha Gupta; Sandeep Punia; Hardeep Singh Tuli (Current Pharmacology Reports, 2021)

Exploration of Heat Stress-Responsive Markers in Understanding Trait Associations in Wheat - P. B. Manjunatha; Nivedita Sinha; Hari Krishna; Divya Chauhan; Pawan Kumar; Ranjeet R. Kumar; Neelu Jain; P. K. Singh; G. P. Singh (Journal of Plant Biology, 2021)

Steviol glycoside accumulation and expression profiling of biosynthetic pathway genes in elicited in vitro cultures of Stevia rebaudiana - Kanika Thakur; Ashrita; Archit Sood; Pawan Kumar; Dinesh Kumar; Ashish R. Warghat (In Vitro Cellular & Developmental Biology - Plant, 2021)

Transgenic cowpea plants expressing Bacillus thuringiensis Cry2Aa insecticidal protein imparts resistance to Maruca vitrata legume pod borer - Anil Kumar; Ranjana Jaiwal; Rohini Sreevathsa; Darshna Chaudhary; Pawan K. Jaiwal (Plant Cell Reports, 2021)

Study of habitat quality assessment using geospatial techniques in Keoladeo National Park, India - Akshita Choudhary; Kundan Deval; Pawan Kumar Joshi (Environmental Science and Pollution Research, 2021)

Air pollution by NO2 and PM2.5 explains COVID-19 infection severity by overexpression of angiotensin-converting enzyme 2 in respiratory cells: a review - Biswaranjan Paital; Pawan Kumar Agrawal (Environmental Chemistry Letters, 2021)

Genome wide annotation and characterization of young, intact long terminal repeat retrotransposons (In-LTR-RTs) of seven legume species - Pawan Kumar Jayaswal; Asheesh Shanker; Nagendra Kumar Singh (Genetica, 2020)

Review of the Analytical Methods for and Clinical Impact of Additives and Flavors Used in Electronic Cigarettes - Vasudha Bansal; Beshare Hashemi; Nadeem Raza; Ki-Hyun Kim; Waseem Raza; Pawan Kumar; Richard J. C. Brown (Exposure and Health, 2020)

Population structure and diversity assessment of barley (Hordeum vulgare L.) introduction from ICARDA - Pawan Kumar; Prabha Banjarey; Rekha Malik; A. N. Tikle; R. P. S. Verma (Journal of Genetics, 2020)

Making Waves Perspectives of Modelling and Monitoring of SARS-CoV-2 in Aquatic Environment for COVID-19 Pandemic - Manish Kumar; Sanjeeb Mohapatra; Payal Mazumder; Ashwin Singh; Ryo Honda; Chuxia Lin; Rina Kumari; Ritusmita Goswami; Pawan Kumar Jha; Meththika Vithanage; Keisuke Kuroda (Current Pollution Reports, 2020)

Myometrial Calcium and Potassium Channels Play a Pivotal Role in Chromium-Induced Relaxation in Rat Uterus: an In Vitro Study - Shirish Bhatiya; Soumen Choudhury; Manju Gari; Pawan Singh; Amit Shukla; Satish Kumar Garg (Biological Trace Element Research, 2020)

Comparative regeneration in six bread wheat (Triticum aestivum L.) varieties from immature and mature scutella for developing efficient and genotype-independent protocol prerequisite for genetic improvement of wheat - Honey Yadav; Kapil Malik; Shashi Kumar; Pawan K. Jaiwal (In Vitro Cellular & Developmental Biology - Plant, 2020)

Determination of water quality of Ganga River System in Himalayan region, referencing indexing techniques - Gagan Matta; Avinash Kumar; Anjali Nayak; Pawan Kumar; Amit Kumar; Ashwani K. Tiwari (Arabian Journal of Geosciences, 2020)

Bioprospecting antioxidants in some non-heterocystous filamentous cyanobacteria inhabit water bodies of semi-arid Rajasthan in India - Anuj Kumar Tomer; Pawan K. Dadheech (Vegetos, 2020)

Morphological and Molecular Characterizations of Guanophilic Fungi of Bats - Pawan Kumar Misra; Neelam Kumari Gautam; Vadamalai Elangovan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Determining limiting factors influencing fish kills at Rewalsar Lake: a case study with reference to Dal Lake (Mcleodganj), western Himalaya, India - Pawan Kumar; Ambrish Kumar Mahajan; Praveen Kumar (Arabian Journal of Geosciences, 2020)

Biocontrol of mosquito vectors through herbal-derived silver nanoparticles: prospects and challenges - Dinesh Kumar; Pawan Kumar; Himmat Singh; Veena Agrawal (Environmental Science and Pollution Research, 2020)

Maximum contaminant level of arsenic in drinking water potentiates quinalphos-induced renal damage on co-administration of both arsenic and quinalphos in Wistar rats - Parvinder Singh; Pawan Kumar Verma; Rajinder Raina; Shilpa Sood; Priyanka Sharma (Environmental Science and Pollution Research, 2020)

Multi criteria study for seismic hazard assessment of UNESCO world heritage Ahmedabad City, Gujarat, Western India - Vinay Kumar Dwivedi; R. K. Dubey; Vasu Pancholi; Madan Mohan Rout; Pawan Singh; B. Sairam; Sumer Chopra; B. K. Rastogi (Bulletin of Engineering Geology and the Environment, 2020)

Modelling Agriculture, Forestry and Other Land Use (AFOLU) in response to climate change scenarios for the SAARC nations - Ram Kumar Singh; Vinay Shankar Prasad Sinha; Pawan Kumar Joshi; Manoj Kumar (Environmental Monitoring and Assessment, 2020)

Correction to: Groundwater geochemical facie: implications of rock-water interaction at the Chamba city (HP), northwest Himalaya, India - Pawan Kumar; Ambrish Kumar Mahajan; Anil Kumar (Environmental Science and Pollution Research, 2020)

Groundwater geochemical facie: implications of rock-water interaction at the Chamba city (HP), northwest Himalaya, India - Pawan Kumar; Ambrish Kumar Mahajan; Anil Kumar (Environmental Science and Pollution Research, 2020)

Investigating use of dimensional limestone slurry waste as fine aggregate in mortar - Harshwardhan Singh Chouhan; Pawan Kalla; Ravindra Nagar; Pradeep Kumar Gautam; Amar Nath Arora (Environment, Development and Sustainability, 2020)

Land use and climate change impacts on distribution of plant species of conservation value in Eastern Ghats, India: a simulation study - Reshma M. Ramachandran; Parth Sarathi Roy; Vishnubhotla Chakravarthi; Pawan Kumar Joshi; J. Sanjay (Environmental Monitoring and Assessment, 2020)

Oleic Acid Prevents Isoprenaline-Induced Cardiac Injury: Effects on Cellular Oxidative Stress, Inflammation and Histopathological Alterations - Pawan Kumar Singh; Manju Gari; Soumen Choudhury; Amit Shukla; Neeraj Gangwar; Satish Kumar Garg (Cardiovascular Toxicology, 2020)

Molecular characterization of chicken astroviruses in gout-affected commercial broiler chickens in Haryana, India - Sumitra Panigrahi; Naresh Jindal; Pawan Kumar; Sanjay Barua; Naveen Kumar; Thachamvally Riyesh; Yogesh Chander (VirusDisease, 2019)

A geo-spatial inter-relationship with drainage morphometry, landscapes and NDVI in the context of climate change: a case study over the Varuna river basin (India) - Pawan Kumar Chaubey; Arnab Kundu; R. K. Mall (Spatial Information Research, 2019)

Current advances and future directions in genetic enhancement of a climate resilient food legume crop, cowpea (Vigna unguiculata L. Walp.) - Meenakshi Sindhu; Anil Kumar; Honey Yadav; Darshna Chaudhary; Ranjana Jaiwal; Pawan K. Jaiwal (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Progress and challenges in electrochemical sensing of volatile organic compounds using metal-organic frameworks - Pawan Kumar; Ki-Hyun Kim; Parveen Kumar Mehta; Liya Ge; Grzegorz Lisak (Critical Reviews in Environmental Science and Technology, 2019)

A proteomic study of cysteine protease induced cell death in anthers of male sterile tobacco transgenic plants - Pawan Shukla; Ranjana Gautam; Naveen Kumar Singh; Israr Ahmed; Pulugurtha Bharadwaja Kirti (Physiology and Molecular Biology of Plants, 2019)

Selection of suitable reference genes for quantitative real-time PCR gene expression analysis in Mulberry (Morus alba L.) under different abiotic stresses - Pawan Shukla; Ramesha A. Reddy; Kangayam M. Ponnuvel; Gulab Khan Rohela; Aftab A. Shabnam; M. K. Ghosh; Rakesh Kumar Mishra (Molecular Biology Reports, 2019)

Amniotic membrane as novel scaffold for human iPSC-derived cardiomyogenesis - Shagufta Parveen; Shishu Pal Singh; M. M. Panicker; Pawan Kumar Gupta (In Vitro Cellular & Developmental Biology - Animal, 2019)

Nephroprotective Potential of Alstonia scholaris in Cisplatin Induced Nephrotoxicity in Experimental Animals - Pawan K. Verma; Rajinder Raina; Mudasir Sultana; Maninder Singh; Pawan Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Molecular cloning and functional analysis of a biphenyl phytoalexin-specific O-methyltransferase from apple cell suspension cultures - Amol Sarkate; Shashank Sagar Saini; Mariam Gaid; Deepa Teotia; Javid Iqbal Mir; Pawan Kumar Agrawal; Ludger Beerhues; Debabrata Sircar (Planta, 2019)

Effect of bifenthrin on oxidative stress parameters in the liver, kidneys, and lungs of rats - Muneer Ahmad Dar; Adil Mehraj Khan; Rajinder Raina; Pawan Kumar Verma; Nasir Manzoor Wani (Environmental Science and Pollution Research, 2019)

Proteomic evaluation of the freshly isolated cyanobionts from Azolla microphylla exposed to salinity stress - Ravindra Kumar Yadav; Keshawanand Tripathi; Vagish Mishra; Pramod Wasudeo Ramteke; Pawan Kumar Singh; Gerard Abraham (Symbiosis, 2019)

Assessment of various genetic components through NCD-I and NCD-III designs of biparental mating in opium poppy - Krishna Nand Maurya; Pawan Kumar Pal; Geeta Asthana; Alka Srivastava; Sudhir Shukla (Journal of Genetics, 2019)

Four New Species of the Genus Pallisentis (Quadrigyridae, Van Cleave, 1920) from Freshwater Fish in Uttar Pradesh, India - Neelam Kumari Gautam; Pawan Kumar Misra; Anand Murai Saxena (Acta Parasitologica, 2019)

Field evaluations of agrochemical toxicity to cyanobacteria in rice field ecosystem: a review - Manish Singh Kaushik; Ajay Kumar; Gerard Abraham; Nalinaxya Prasad Dash; Pawan Kumar Singh (Journal of Applied Phycology, 2019)

Evaluation of trophic status and its limiting factors in the Renuka Lake of Lesser Himalaya, India - Pawan Kumar; Ambrish Kumar Mahajan; Narendra Kumar Meena (Environmental Monitoring and Assessment, 2019)

Cold survival strategies for bacteria, recent advancement and potential industrial applications - Amit S. Dhaulaniya; Biji Balan; Mohit kumar; Pawan K. Agrawal; Dileep Kumar Singh (Archives of Microbiology, 2019)

Protective Mechanisms of Quercetin on Cisplatin Induced Oxidative Damage in Hepatic Tissue of Wistar Rats - Pawan K. Verma; Rajinder Raina; Shahid Prawez; Mudasir Sultana; Maninder Singh; Pawan Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Trait anxiety and neural efficiency of abstract reasoning: An fMRI investigation - Shilpi Modi; Mukesh Kumar; Sanjeev Nara; Pawan Kumar; Subash Khushu (Journal of Biosciences, 2018)

Monitoring of seasonal variability and movement of suspended sediment concentrations along the Thiruvananthapuram coast, southern India, using the Landsat OLI sensor - Bismay Ranjan Tripathy; Kaliraj Seenipandi; Haroon Sajjad; Pawan Kumar Joshi; Bhagwan Singh Chaudhary; Pavan Kumar (Ocean Science, 2018)
Studies on suspended sediment concentrations at a seasonal scale play a vital role in understanding coastal hydrodynamic processes in an area. Assessment of spatio-temporal changes in suspended sediments in nearshore areas has gained complexity due to the utilization of conventional methods; this issue can be successfully solved nowadays using multi-temporal remotely sensed images with the help of advanced image processing techniques. The present study is an attempt to demonstrate the model algorithm used to extract suspended sediment concentrations using Landsat 8 OLI (Operational Land Imager) sensor images. The study was executed in a near-offshore area of the Thiruvananthapuram coast, southern India, and focused on the extraction of suspended sediment concentrations and their seasonal variability during pre-monsoon and post-monsoon periods. The OLI images were pre-processed to obtain the actual reflectance using the FLASSH module of the ENVI v5.5 software. The generic model developed herein is designed to compute the spectral reflectance variability between coastal water and suspended sediments and to differentiate the spatial accumulation of the suspended sediment concentrations from the coastal water at the pixel scale. Maximum (0.8 % in near-infrared bands) and minimum (0.6 % in blue bands) spectral reflectance indicates the occurrence of suspended sediments in the coastal water. The model-derived results revealed that the suspended sediment concentration gradually decreased with increasing depth and distance from the shoreline. Higher sediment concentrations accumulated at lower depths in coastal water due to wave and current action that seasonally circulated the sediments. This higher concentration of the suspended sediment load was estimated to be 0.92 mg L−1 at the shallow depths (

Correction to: Analysis of Promiscuous T cell Epitopes for Vaccine Development Against West Nile Virus Using Bioinformatics Approaches - Pawan Sharma; Priti Sharma; Sukrit Srivastav; Sanjay Mishra; Ajay Kumar (International Journal of Peptide Research and Therapeutics, 2018)

Analysis of Promiscuous T cell Epitopes for Vaccine Development Against West Nile Virus Using Bioinformatics Approaches - Pawan Sharma; Priti Sharma; Sanjay Mishra; Ajay Kumar (International Journal of Peptide Research and Therapeutics, 2018)

Morphological and molecular diversity of Sclerotinia sclerotiorum infecting Indian mustard - A. S. Rathi; Minakshi Jattan; Rakesh Punia; Subaran Singh; Pawan Kumar; Ram Avtar (Indian Phytopathology, 2018)

Vulnerability of forests in the Himalayan region to climate change impacts and anthropogenic disturbances: a systematic review - Anusheema Chakraborty; Somidh Saha; Kamna Sachdeva; Pawan Kumar Joshi (Regional Environmental Change, 2018)

Coupling of 1D models (SWAT and SWMM) with 2D model (iRIC) for mapping inundation in Brahmani and Baitarani river delta - Pawan Kumar Rai; C. T. Dhanya; B. R. Chahar (Natural Hazards, 2018)

Practical breeding strategies to improve resistance to Septoria tritici blotch of wheat - Seyed Mahmoud Tabib Ghaffary; Aakash Chawade; Pawan Kumar Singh (Euphytica, 2018)

Estimating Tunnel Strain in the Weak and Schistose Rock Mass Influenced by Stress Anisotropy: An Evaluation Based on Three Tunnel Cases from Nepal - Krishna Kanta Panthi; Pawan Kumar Shrestha (Rock Mechanics and Rock Engineering, 2018)

Salinity induced changes in the chloroplast proteome of the aquatic pteridophyte Azolla microphylla - Preeti Thagela; Ravindra Kumar Yadav; Keshawanand Tripathi; Pawan Kumar Singh; Altaf Ahmad; Anil Dahuja; Gerard Abraham (Symbiosis, 2018)

Comparative transcriptomics uncovers differences in photoautotrophic versus photoheterotrophic modes of nutrition in relation to secondary metabolites biosynthesis in Swertia chirayita - Tarun Pal; Jibesh Kumar Padhan; Pawan Kumar; Hemant Sood; Rajinder S. Chauhan (Molecular Biology Reports, 2018)

Insights into maize genome editing via CRISPR/Cas9 - Astha Agarwal; Pranjal Yadava; Krishan Kumar; Ishwar Singh; Tanushri Kaul; Arunava Pattanayak; Pawan Kumar Agrawal (Physiology and Molecular Biology of Plants, 2018)

Toxicity of biocides to native cyanobacteria at different rice crop stages in wetland paddy field - Nalinaxya Prasad Dash; Manish Singh Kaushik; Ajay Kumar; Gerard Abraham; Pawan Kumar Singh (Journal of Applied Phycology, 2018)

Seasonal variations in size distribution, water-soluble ions, and carbon content of size-segregated aerosols over New Delhi - Pawan Kumar; Sushil Kumar; Sudesh Yadav (Environmental Science and Pollution Research, 2018)

Hydrochemistry and water quality of Rewalsar Lake of Lesser Himalaya, Himachal Pradesh, India - Pawan Kumar Gaury; Narendra Kumar Meena; A. K. Mahajan (Environmental Monitoring and Assessment, 2018)

Transcriptomes of Podophyllum hexandrum unravel candidate miRNAs and their association with the biosynthesis of secondary metabolites - Pawan Kumar; Jibesh Kumar Padhan; Ashwani Kumar; Rajinder S. Chauhan (Journal of Plant Biochemistry and Biotechnology, 2018)

Yield and Soil Organic Matter Dynamics as Affected by the Long-Term Use of Organic and Inorganic Fertilizers Under Rice–Wheat Cropping System in Subtropical Mollisols - Pawan Kumar Pant; Shri Ram; Veer Singh (Agricultural Research, 2017)

Review of the quantification techniques for polycyclic aromatic hydrocarbons (PAHs) in food products - Vasudha Bansal; Pawan Kumar; Eilhann E. Kwon; Ki-Hyun Kim (Critical Reviews in Food Science and Nutrition, 2017)

Capturing forest dependency in the central Himalayan region: Variations between Oak (Quercus spp.) and Pine (Pinus spp.) dominated forest landscapes - Anusheema Chakraborty; Pawan Kumar Joshi; Kamna Sachdeva (Ambio, 2017)

Bacillus algicola decolourises more than 95% of some textile azo dyes - Pawan Kumar Chukowry; Ackmez Mudhoo; Sunita J. Santchurn (Environmental Chemistry Letters, 2017)

Geoinformatics for assessing the inferences of quantitative drainage morphometry of the Narmada Basin in India - Praveen Kumar Rai; Pawan Kumar Chaubey; Kshitij Mohan; Praful Singh (Applied Geomatics, 2017)

Implicating the potential role of orexin in hypertension - Monika Rani; Raghuvansh Kumar; Pawan Krishan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Sequence and Structure Based Binding Prediction Study of HLA Class I and cTAP Binding Peptides for Japanese Encephalitis Vaccine Development - Pawan Sharma; Sukrit Srivastav; Sanjay Mishra; Ajay Kumar (International Journal of Peptide Research and Therapeutics, 2017)

Sample preparation method for tissue based proteomic analysis of Azolla microphylla - Preeti Thagela; Ravindra Kumar Yadav; Vagish Mishra; Keshawanand Tripathi; Altaf Ahmad; Anil Dahuja; Pawan Kumar Singh; Gerard Abraham (Symbiosis, 2017)

RNA-Seq reveals the molecular mechanism of trapping and killing of root-knot nematodes by nematode-trapping fungi - Ramesh Pandit; Reena Patel; Namrata Patel; Vaibhav Bhatt; Chaitanya Joshi; Pawan Kumar Singh; Anju Kunjadia (World Journal of Microbiology and Biotechnology, 2017)

Nitrogenous agrochemicals inhibiting native diazotrophic cyanobacterial contribution in wetland rice ecosystem - Nalinaxya Prasad Dash; Ajay Kumar; Manish Singh Kaushik; Gerard Abraham; Pawan Kumar Singh (Journal of Applied Phycology, 2017)

Salinity-induced inhibition of growth in the aquatic pteridophyte Azolla microphylla primarily involves inhibition of photosynthetic components and signaling molecules as revealed by proteome analysis - Preeti Thagela; Ravindra Kumar Yadav; Vagish Mishra; Anil Dahuja; Altaf Ahmad; Pawan Kumar Singh; Budhi Sagar Tiwari; Gerard Abraham (Protoplasma, 2017)

Comparative whole-transcriptome analysis in Podophyllum species identifies key transcription factors contributing to biosynthesis of podophyllotoxin in P. hexandrum - Pawan Kumar; Varun Jaiswal; Tarun Pal; Jagdish Singh; Rajinder S. Chauhan (Protoplasma, 2017)

Cyanobacterial (unicellular and heterocystous) biofertilization to wetland rice influenced by nitrogenous agrochemical - N. P. Dash; Ajay Kumar; Manish Singh Kaushik; Pawan Kumar Singh (Journal of Applied Phycology, 2016)

An indicator-based approach to assess village-level social and biophysical vulnerability of agriculture communities in Uttarakhand, India - Roopam Shukla; Kamna Sachdeva; Pawan Kumar Joshi (Journal of Mountain Science, 2016)

Seasonal life cycle of Holotrichia longipennis (Blanchard ) (Coleoptera: Scarabaeidae: Melolonthinae): a serious foliage and root feeding pest in India - Mandeep Pathania; Ravinder Singh Chandel; Kuldeep Singh Verma; Pawan Kumar Mehta (Phytoparasitica, 2016)

Water-soluble ions and carbon content of size-segregated aerosols in New Delhi, India: direct and indirect influences of firework displays - Pawan Kumar; Rakesh Kumar; Sudesh Yadav (Environmental Science and Pollution Research, 2016)

Multi-temporal forest cover dynamics in Kashmir Himalayan region for assessing deforestation and forest degradation in the context of REDD+ policy - Akhlaq Amin Wani; Pawan Kumar Joshi; Ombir Singh; Sumera Shafi (Journal of Mountain Science, 2016)

Toxicophore exploration as a screening technology for drug design and discovery: techniques, scope and limitations - Pankaj Kumar Singh; Arvind Negi; Pawan Kumar Gupta; Monika Chauhan; Raj Kumar (Archives of Toxicology, 2016)

Use of Geospatial Tools to Prioritize Zones of Hydro-Energy Potential in Glaciated Himalayan Terrain - Lydia Sam; Anshuman Bhardwaj; Vinay S P Sinha; Pawan K Joshi; Rajesh Kumar (Journal of the Indian Society of Remote Sensing, 2016)

15d-Prostaglandin J2 induced reactive oxygen species-mediated apoptosis during experimental visceral leishmaniasis - Preeti Vishwakarma; Naveen Parmar; Pawan Kumar Yadav; Pragya Chandrakar; Susanta Kar (Journal of Molecular Medicine, 2016)

Estimation of Sea Surface Temperature (SST) Using Marine Seismic Data - Satish Kumar Sinha; Pawan Dewangan; Kalachand Sain (Pure and Applied Geophysics, 2016)

Quinolone co-resistance in ESBL- or AmpC-producing Escherichia coli from an Indian urban aquatic environment and their public health implications - Priyanka Bajaj; Pawan Kumar Kanaujia; Nambram Somendro Singh; Shalu Sharma; Shakti Kumar; Jugsharan Singh Virdi (Environmental Science and Pollution Research, 2016)

Estimation of particulate matter from satellite- and ground-based observations over Hyderabad, India - P.R. Sinha; Pawan Gupta; D.G. Kaskaoutis; L.K. Sahu; N. Nagendra; R. K. Manchanda; Y. B. Kumar; S. Sreenivasan (International Journal of Remote Sensing, 2015)

Abundance and Spatio-Temporal Distributional Pattern of Dotilla Myctiroides (Milne-Edwards) on Exposed Sandy Beach of Aksa, Mumbai - Shahnawaz Ali; S. K. Chakraborty; Pawan Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Differential neural activation for camouflage detection task in Field-Independent and Field-Dependent individuals: Evidence from fMRI - Janani Rajagopalan; Shilpi Modi; Pawan Kumar; Subash Khushu; Manas K Mandal (Journal of Biosciences, 2015)

Chromosome counts, chromosomal pairing, and pollen fertility in thirty-eight species of Asteraceae from Pangi Valley in District Chamba of Himachal Pradesh (India) - Pawan Kumar Rana; Puneet Kumar; Vijay Kumar Singhal (Brazilian Journal of Botany, 2015)

Effect of microwave treatment on air permeability and preservative impregnation of Eucalyptus tereticornis wood - Pawan Kumar Poonia; Sadhna Tripathi; Kapil Sihag; Shailendra Kumar (Journal of the Indian Academy of Wood Science, 2015)

Global Fluoride Occurrence, Available Technologies for Fluoride Removal, and Electrolytic Defluoridation: A Review - Neha Mumtaz; Govind Pandey; Pawan Kumar Labhasetwar (Critical Reviews in Environmental Science and Technology, 2015)

Expression analysis of biosynthetic pathway genes vis-à-vis podophyllotoxin content in Podophyllum hexandrum Royle - Pawan Kumar; Tarun Pal; Neha Sharma; Varun Kumar; Hemant Sood; Rajinder S. Chauhan (Protoplasma, 2015)

Assessment of the effect of stress anisotropy on tunnel deformation in the Kaligandaki project in the Nepal Himalaya - Pawan Kumar Shrestha; Krishna Kanta Panthi (Bulletin of Engineering Geology and the Environment, 2015)

In-vitro Anthelmintic Efficacy of Aqueous Extract of Scindapsus officinalis (Roxb.) Schott Fruits Against Haemonchus contortus of Small Ruminants - Gagandeep Singh; Rajeev Singh; Pawan Kumar Verma; Rajiv Singh; Atul Anand (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Natural allelic diversity in OsDREB1F gene in the Indian wild rice germplasm led to ascertain its association with drought tolerance - Bikram Pratap Singh; Pawan Kumar Jayaswal; Balwant Singh; Pankaj Kumar Singh; Vinod Kumar; Shefali Mishra; Nisha Singh; Kabita Panda; Nagendra Kumar Singh (Plant Cell Reports, 2015)

Global Fluoride Occurrence, Available Technologies for Fluoride Removal and Electrolytic Defluoridation: A Review - Neha Mumtaz; Govind Pandey; Pawan Kumar Labhasetwar (Critical Reviews in Environmental Science and Technology, 2015)

Characterization of a vacuolar processing enzyme expressed in Arachis diogoi in resistance responses against late leaf spot pathogen, Phaeoisariopsis personata - Dilip Kumar; Sakshi Rampuria; Naveen Kumar Singh; Pawan Shukla; P. B. Kirti (Plant Molecular Biology, 2015)

Circulating nucleic acids damage DNA of healthy cells by integrating into their genomes - Indraneel Mittra; Naveen Kumar Khare; Gorantla Venkata Raghuram; Rohan Chaubal; Fatema Khambatti; Deepika Gupta; Ashwini Gaikwad; Preeti Prasannan; Akshita Singh; Aishwarya Iyer; Ankita Singh; Pawan Upadhyay; et al. (Journal of Biosciences, 2015)

Geospatial quantification and analysis of environmental changes in urbanizing city of Kolkata (India) - Richa Sharma; Anusheema Chakraborty; Pawan Kumar Joshi (Environmental Monitoring and Assessment, 2015)

Habitat Attributes and Waterbird-Use of Four Wetlands in Manas National Park, Assam, India - Barnali Sarkar; Prantik Hazra; S. Pawan Kumar; Piu Ghosh; Archita Banerjee; T. N. Khan (Proceedings of the Zoological Society, 2014)

Alterations in Plasma and Tissue Acetylcholinesterase Activity Following Repeated Oral Exposure of Chlorpyrifos Alone and in Conjunction with Fluoride in Wistar Rats - Naseer Ahmad Baba; Rajinder Raina; Pawan Kumar Verma; Mudasir Sultana (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Functional Role of Amino Acid Neurotransmitters on Spontaneous Muscular Activity of Paramphistomum cervi from Ruminants - Chandana C. Barua; Snigdha Hazarika; Beenita Saikia; Arabinda Phukan; Debesh Pathak; Rumi S. Borah; Acheenta Gohain Barua; Pawan Kumar Verma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Sources and processes governing rainwater chemistry in New Delhi, India - Pawan Kumar; Sudesh Yadav; Abhay Kumar (Natural Hazards, 2014)

Pollutant scavenging in dew water collected from an urban environment and related implications - Sudesh Yadav; Pawan Kumar (Air Quality, Atmosphere & Health, 2014)

Distribution Network Assessment using EPANET for Intermittent and Continuous Water Supply - Sanjeeb Mohapatra; Aabha Sargaonkar; Pawan Kumar Labhasetwar (Water Resources Management, 2014)

Implementation of water safety plan for a large-piped water supply system - Anisha Nijhawan; Priyanka Jain; Aabha Sargaonkar; Pawan Kumar Labhasetwar (Environmental Monitoring and Assessment, 2014)

Does toll-like receptor-3 (TLR-3) have any role in Indian AMD phenotype? - Neel Kamal Sharma; Kaushal Sharma; Amod Gupta; Sudesh Prabhakar; Ramandeep Singh; Pawan Kumar Gupta; Akshay Anand (Molecular and Cellular Biochemistry, 2014)

Analysis of the plastic deformation behavior of schist and schistose mica gneiss at Khimti headrace tunnel, Nepal - Pawan Kumar Shrestha; Krishna Kanta Panthi (Bulletin of Engineering Geology and the Environment, 2014)

Chromosome numbers, characterization of chromosomal pairing during meiosis, origin and natural propagation in polyploid cytotypes (4x, 5x and 6x) of Agrimonia eupatoria L. (Rosaceae) in northwest Himalayas (India) - Puneet Kumar; Pawan K. Rana; Himshikha; Vijay Kumar Singhal; R. C. Gupta (Protoplasma, 2014)

Basal cGMP regulates the resting pacemaker potential frequency of cultured mouse colonic interstitial cells of Cajal - Pawan Kumar Shahi; Seok Choi; Yu Jin Jeong; Chan Guk Park; Insuk So; Jae Yeoul Jun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Antibacterial and free radical scavenging potential of synthesized 7-hydroxy-2-aryl-6-aryldiazenyl-4H-chromen-4-ones - Pawan Kumar Sharma; Prabal Bandyopadhyay; Pratibha Sharma; Ashok Kumar (Medicinal Chemistry Research, 2014)

Re-evaluation of the inheritance for root-knot nematode resistance in the Upland cotton germplasm line M-120 RNR revealed two epistatic QTLs conferring resistance - Yajun He; Pawan Kumar; Xinlian Shen; Richard F. Davis; Guillermo Van Becelaere; O. Lloyd May; Robert L. Nichols; Peng W. Chee (Theoretical and Applied Genetics, 2014)

Anti-Hyperglycemic, Anti-Hyperlipidemic and Antioxidant Potential of Alcoholic-Extract of Sida cordifolia (Areal Part) in Streptozotocin-Induced-Diabetes in Wistar-Rats - Mahrukh Ahmad; Shahid Prawez; Mudasir Sultana; Rajinder Raina; Nrip Kishore Pankaj; Pawan Kumar Verma; Shafiqur Rahman (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Male meiosis, morphometric analysis and natural propagation in the 2× and 3× cytotypes of Tordyliopsis brunonis (Apiaceae) from northwest Himalayas (India) - Puneet Kumar; Pawan Kumar Rana; Vijay Kumar Singhal (Plant Systematics and Evolution, 2014)

Immunophenotypic characterization and tenogenic differentiation of mesenchymal stromal cells isolated from equine umbilical cord blood - Niharika Mohanty; Baldev R. Gulati; Rajesh Kumar; Sandeep Gera; Pawan Kumar; Rajesh K. Somasundaram; Sandeep Kumar (In Vitro Cellular & Developmental Biology - Animal, 2014)

Expression of a pathogen-induced cysteine protease (AdCP) in tapetum results in male sterility in transgenic tobacco - Pawan Shukla; Naveen Kumar Singh; Dilip Kumar; Sambasivam Vijayan; Israr Ahmed; Pulugurtha Bharadwaja Kirti (Functional & Integrative Genomics, 2014)

Groundwater Effect on Faulted Rock Mass: An Evaluation of Modi Khola Pressure Tunnel in the Nepal Himalaya - Pawan Kumar Shrestha; Krishna Kanta Panthi (Rock Mechanics and Rock Engineering, 2014)

Cytogeography and phenomenon of cytomixis in Silene vulgaris from cold regions of Northwest Himalayas (India) - Puneet Kumar; Pawan Kumar Rana; Himshikha; Vijay Kumar Singhal; Raghbir Chand Gupta (Plant Systematics and Evolution, 2014)

Benzenesulfonamide bearing pyrazolylpyrazolines: synthesis and evaluation as anti-inflammatory–antimicrobial agents - Pawan Kumar; Navneet Chandak; Pawan Kaushik; Chetan Sharma; Dhirender Kaushik; Kamal R. Aneja; Pawan K. Sharma (Medicinal Chemistry Research, 2014)

Exploration of antimicrobial potential of pyrazolo[3,4-b]pyridine scaffold bearing benzenesulfonamide and trifluoromethyl moieties - Navneet Chandak; Satish Kumar; Pawan Kumar; Chetan Sharma; Kamal R. Aneja; Pawan K. Sharma (Medicinal Chemistry Research, 2013)

Effect of Sub-Acute Oral Exposure of Bifenthrin on Biochemical Parameters in Crossbred Goats - Adil Mehraj Khan; Mudasir Sultana; Rajinder Raina; Nitin Dubey; Pawan Kumar Verma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Implications of climate change on streamflow of a snow-fed river system of the Northwest Himalaya - Vaibhav Sharma; Varunendra Dutta Mishra; Pawan Kumar Joshi (Journal of Mountain Science, 2013)
Air temperature and snow cover variability are sensitive indicators of climate change. This study was undertaken to forecast and quantify the potential streamflow response to climate change in the Jhelum River basin. The implications of air temperature trends (+0.11°C/decade) reported for the entire north-west Himalaya for past century and the regional warming (+0.7°C/decade) trends of three observatories analyzed between last two decades were used for future projection of snow cover depletion and stream flow. The streamflow was simulated and validated for the year 2007–2008 using snowmelt runoff model (SRM) based on in-situ temperature and precipitation with remotely sensed snow cover area. The simulation was repeated using higher values of temperature and modified snow cover depletion curves according to the assumed future climate. Early snow cover depletion was observed in the basin in response to warmer climate. The results show that with the increase in air temperature, streamflow pattern of Jhelum will be severely affected. Significant redistribution of streamflow was observed in both the scenarios. Higher discharge was observed during spring-summer months due to early snowmelt contribution with water deficit during monsoon months. Discharge increased by 5%–40% during the months of March to May in 2030 and 2050. The magnitude of impact of air temperature is higher in the scenario-2 based on regional warming. The inferences pertaining to change in future streamflow pattern can facilitate long term decisions and planning concerning hydro-power potential, water resource management and flood hazard mapping in the region.

Effect of Repeated Oral Administration of Bifenthrin on Lipid Peroxidation and Anti-oxidant Parameters in Wistar Rats - Muneer Ahmad Dar; Adil Mehraj Khan; Rajinder Raina; Pawan Kumar Verma; Mudasir Sultana (Bulletin of Environmental Contamination and Toxicology, 2013)

Cryopreservation and Quality Assessment of Buffalo Bull Semen Collected from Farmer’s Doorstep - Pawan Singh; D. Kumar; Pradeep Kumar; Inderjeet Singh; P. S. Yadav (Agricultural Research, 2013)

Factors Affecting Nutrient Concentration and Stable Carbon and Nitrogen Isotope Ratio of Particulate Organic Matter in the Ishikari River System, Japan - Pawan Kumar Jha; Minagawa Masao (Water, Air, & Soil Pollution, 2013)

Isolation and characterization of gut bacteria of fruit fly, Bactrocera tau (Walker) - Chandra S. Prabhakar; Pankaj Sood; Sarbjit S. Kanwar; Prem N. Sharma; Ajay Kumar; Pawan K. Mehta (Phytoparasitica, 2013)

Spatio-temporal footprints of urbanisation in Surat, the Diamond City of India (1990–2009) - Richa Sharma; Aniruddha Ghosh; Pawan Kumar Joshi (Environmental Monitoring and Assessment, 2013)

Factors and sources influencing ionic composition of atmospheric condensate during winter season in lower troposphere over Delhi, India - Pawan Kumar; Sudesh Yadav (Environmental Monitoring and Assessment, 2013)

Enhanced heterodimerization of Bax by Bcl-2 mutants improves irradiated cell survival - Yogesh Kumar Verma; Pawan Kumar Raghav; Hanumantharao Guru Raj; Rajendra Prasad Tripathi; Gurudutta U. Gangenahalli (Apoptosis, 2013)

Heteroaromatic analogues of 1,5-diarylpyrazole class as anti-inflammatory agents - Pawan K. Sharma; Nisha Chandna; Surender Kumar; Pawan Kumar; Satish Kumar; Pawan Kaushik; Dhirender Kaushik (Medicinal Chemistry Research, 2012)

Synthesis and biological evaluation of some pyrazole derivatives as anti-inflammatory–antibacterial agents - Pawan Kumar; Navneet Chandak; Pawan Kaushik; Chetan Sharma; Dhirender Kaushik; Kamal R. Aneja; Pawan K. Sharma (Medicinal Chemistry Research, 2012)

Synthesis of 1-(4-aminosulfonylphenyl)-3,5-diarylpyrazoline derivatives as potent antiinflammatory and antimicrobial agents - Pawan K. Sharma; Satish Kumar; Pawan Kumar; Pawan Kaushik; Chetan Sharma; Dhirender Kaushik; Kamal R. Aneja (Medicinal Chemistry Research, 2012)

Synthesis and evaluation of 4-(substituted)-acetylamino-3-mercapto-5-(4-substituted) phenyl-1,2,4-triazole derivatives as antimicrobial agents - Neeraj Upmanyu; Sanjay Kumar; Pawan Porwal; Kamal Shah; Pradeep Mishra (Medicinal Chemistry Research, 2012)

In vivo differentiation potential of buffalo (Bubalus bubalis) embryonic stem cell - Om Prakash Verma; Rajesh Kumar; Amar Nath; Manjinder Sharma; Pawan Kumar Dubey; G. Sai Kumar; G. Taru Sharma (In Vitro Cellular & Developmental Biology - Animal, 2012)

Highly Expressed Recombinant SEB for Antibody Production and Development of Immunodetection System - Ranu Agrawal; Pawan Kumar Singh; Sushil Kumar Sharma; D. V. Kamboj; Ajay Kumar Goel; Lokendra Singh (Indian Journal of Microbiology, 2012)

Pathological study of non-neoplastic urinary bladder lesions in cattle and buffaloes: a preliminary report - Ramesh Somvanshi; Sonia Pathania; Nagappan Nagarajan; Kanchan Pangty; Pawan Kumar (Tropical Animal Health and Production, 2012)

Expression and quantification of Oct-4 gene in blastocyst and embryonic stem cells derived from in vitro produced buffalo embryos - Manjinder Sharma; Rajesh Kumar; Pawan K. Dubey; Om Prakash Verma; Amar Nath; G. Saikumar; G. Taru Sharma (In Vitro Cellular & Developmental Biology - Animal, 2012)

In vivo analysis of translation initiation sites in Plasmodium falciparum - Balakota Reddy Patakottu; Prashant Kumar Singh; Pawan Malhotra; V. S. Chauhan; Swati Patankar (Molecular Biology Reports, 2012)

The first draft of the pigeonpea genome sequence - Nagendra K. Singh; Deepak K. Gupta; Pawan K. Jayaswal; Ajay K. Mahato; Sutapa Dutta; Sangeeta Singh; Shefali Bhutani; Vivek Dogra; Bikram P. Singh; Giriraj Kumawat; Jitendra K. Pal; Awadhesh Pandit; et al. (Journal of Plant Biochemistry and Biotechnology, 2012)

Persistent occurrence of meiotic abnormalities in a new hexaploid cytotype of Thalictrum foetidum from Indian cold deserts - Vijay Kumar Singhal; Pawan Kumar Rana; Puneet Kumar; Dalvir Kaur (Biologia, 2011)

National Forest Policy in India: Critique of Targets and Implementation - Aditya Kumar Joshi; Pallavi Pant; Prasant Kumar; Amarnath Giriraj; Pawan Kumar Joshi (Small-scale Forestry, 2011)

Synthesis and anti-inflammatory evaluation of some pyrazolo[3,4-b]pyridines - Pawan K. Sharma; Karan Singh; Surender Kumar; Pawan Kumar; S. N. Dhawan; Sukhbir Lal; Holger Ulbrich; Gerd Dannhardt (Medicinal Chemistry Research, 2011)

Growth and biochemical characterization of associations between cyanobionts and wheat seedlings in co-culturing experiments - Anjuli Sood; Pawan K. Singh; Arun Kumar; Rajendra Singh; Radha Prasanna (Biologia, 2011)

Landscape approach for quantifying land use land cover change (1972–2006) and habitat diversity in a mining area in Central India (Bokaro, Jharkhand) - Sumedha Malaviya; Madhushree Munsi; Gracy Oinam; Pawan Kumar Joshi (Environmental Monitoring and Assessment, 2010)

Age-Dependent Changes in Glutathione-S-Transferase: Correlation with Total Plasma Antioxidant Potential and Red Cell Intracellular Glutathione - Pawan Kumar Maurya; Syed Ibrahim Rizvi (Indian Journal of Clinical Biochemistry, 2010)

Bacterial biodiversity from Roopkund Glacier, Himalayan mountain ranges, India - Suman Pradhan; T. N. R. Srinivas; Pavan Kumar Pindi; K. Hara Kishore; Z. Begum; Pawan Kumar Singh; Ashish Kumar Singh; M. S. Pratibha; Arun K. Yasala; G. S. N. Reddy; S. Shivaji (Extremophiles, 2010)

Alterations in Electrocardiographic Parameters after Subacute Exposure of Fluoride and Ameliorative Action of Aluminium Sulphate in Goats - Vinay Kant; Anil Kumar Srivastava; Pawan Kumar Verma; Rajinder Raina; Nrip Kishore Pankaj (Biological Trace Element Research, 2010)

Evaluating the potential of N. calcicola and its bicarbonate resistant mutant as bioameleorating agents for ‘usar’ soil - Pranita Jaiswal; Ajai Kumar Kashyap; Radha Prasanna; Pawan Kumar Singh (Indian Journal of Microbiology, 2010)

Neuropeptide α-MSH exerts pro-inflammatory effects on Neisseria meningitidis infection in vitro - Pawan Kumar; Jeannette N. Williams; Kesta L. Durkin; John E. Heckels; Peter S. Friedmann; Eugene Healy; Myron Christodoulides (Inflammation Research, 2010)

Protective role of tea catechins on erythrocytes subjected to oxidative stress during human aging - Pawan Kumar Maurya; Syed Ibrahim Rizvi (Natural Product Research, 2009)

Genome-wide QTL analysis for pre-harvest sprouting tolerance in bread wheat - Amita Mohan; Pawan Kulwal; Ravinder Singh; Vinay Kumar; Reyazul Rouf Mir; Jitendra Kumar; Manoj Prasad; H. S. Balyan; P. K. Gupta (Euphytica, 2009)

Alterations in Biochemical Parameters During Subacute Toxicity of Fluoride Alone and in Conjunction with Aluminum Sulfate in Goats - Vinay Kant; Anil Kumar Srivastava; Pawan Kumar Verma; Rajinder Raina (Biological Trace Element Research, 2009)

Biodegradation of high explosive production effluent containing RDX and HMX by denitrifying bacteria - Rita Singh; Pramod Soni; Pawan Kumar; Sumita Purohit; Antaryami Singh (World Journal of Microbiology and Biotechnology, 2009)

Assessment of the impact of landfill on groundwater quality: A case study of the Pirana site in western India - Umesh Kumar Singh; Manish Kumar; Rita Chauhan; Pawan Kumar Jha; AL. Ramanathan; V. Subramanian (Environmental Monitoring and Assessment, 2008)

The application of satellite data for the quantification of mangrove loss and coastal management in the Godavari estuary, East Coast of India - D. R. Satapathy; R. J. Krupadam; L. Pawan Kumar; S. R. Wate (Environmental Monitoring and Assessment, 2007)

QTL analysis for some quantitative traits in bread wheat - Kumar Gupta Pushpendra; Singh Balyan Harindra; Laxminarayan Kulwal Pawan; Kumar Neeraj; Kumar Ajay; Rouf Mir Reyazul; Mohan Amita; Kumar Jitendra (Journal of Zhejiang University-SCIENCE B, 2007)

Impact of Distillery Soil Leachate on Haematology of Swiss Albino Mice (Mus musculus) - Subhasini Sharma; Arti Sharma; Pawan Kumar Singh; Pratima Soni; Shweta Sharma; Pradeep Sharma; K. P. Sharma (Bulletin of Environmental Contamination and Toxicology, 2007)

QTL mapping for resistance to root-knot nematodes in the M-120 RNR Upland cotton line (Gossypium hirsutum L.) of the Auburn 623 RNR source - Xinlian Shen; Guillermo Van Becelaere; Pawan Kumar; Richard F. Davis; O. Lloyd May; Peng Chee (Theoretical and Applied Genetics, 2006)

QTL analysis for grain weight in common wheat - Neeraj Kumar; Pawan L. Kulwal; Anupama Gaur; Akhilesh K. Tyagi; Jitendra P. Khurana; Paramjit Khurana; Harindra S. Balyan; Pushpendra K. Gupta (Euphytica, 2006)

Defect in mitochondrial functions in damaged human mitral valve - Santosh Shinde; Pawan Kumar; Kaushala Mishra; Neela Patil (Indian Journal of Clinical Biochemistry, 2006)

Gene networks in hexaploid wheat: interacting quantitative trait loci for grain protein content - Pawan Kulwal; Neeraj Kumar; Ajay Kumar; Raj Kumar Gupta; Harindra Singh Balyan; Pushpendra Kumar Gupta (Functional & Integrative Genomics, 2005)

Aerial pollen diversity in India and their clinical significance in allergic diseases - A. B. Singh; Pawan Kumar (Indian Journal of Clinical Biochemistry, 2004)

Radiation Processed Amniotic Membranes in the Treatment of Non-Healing Ulcers of Different Etiologies - Rita Singh; U.S. Chouhan; Sumita Purohit; Pallavi Gupta; Pawan Kumar; Ashok Kumar; M.P. Chacharkar; Dilip Kachhawa; B.C. Ghiya (Cell and Tissue Banking, 2004)

Properties of Air Dried Radiation Processed Amniotic Membranes under Different Storage Conditions - Rita Singh; Pallavi Gupta; Pawan Kumar; Ashok Kumar; M.P. Chacharkar (Cell and Tissue Banking, 2003)

Expression of neuronal plasticity markers in hypoglycemia induced brain injury - Pawan Singh; Pawan Kumar Heera; Gurcharan Kaur (Molecular and Cellular Biochemistry, 2003)

Enhanced production of penicillin G acylase from a recombinant Escherichia coli - Pawan Kumar Vohra; Rakesh Sharma; Des Raj Kashyap; Rupinder Tewari (Biotechnology Letters, 2001)

Adriamycin-induced heart failure: mechanisms and modulation - Pawan Singal; Timao Li; Dinender Kumar; Igor Danelisen; Natasha Iliskovic (Molecular and Cellular Biochemistry, 2000)

Adriamycin depresses in vivo and in vitro phosphatidylethanolamine N-methylation in rat heart sarcolemma - Natasha Iliskovic; Vincenzo Panagia; Ján Slezák; Dinender Kumar; Timao Li; Pawan K. Singal (Molecular and Cellular Biochemistry, 1997)